Liquid laundry detergent composition
Patent Information
- Application Number
- CN202580020538.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-26
- Filing Date
- 2025-03-06
- Publication Date
- 2026-10-16
AI Technical Summary
[0038] The liquid laundry detergent composition of the present invention comprises the above-described structure and contains biodegradable additives, exhibiting excellent cleaning performance when used as a liquid laundry detergent, and is therefore suitable for use in concentrated liquid laundry detergents, etc.
Smart Images

Figure CN122935596A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a liquid laundry detergent composition. More specifically, it relates to a liquid laundry detergent composition for use in concentrated liquid laundry detergents and the like. Background Technology
[0002] Detergents with surfactants as the main component have been developed into various types, such as those for clothing and tableware.
[0003] In addition to surfactants, detergents also use various detergent additives, such as polyvinyl alcohol (see, for example, Patent Documents 1-5).
[0004] In recent years, the demand for water-soluble liquid laundry detergents has increased due to the widespread use of front-loading washing machines that can wash with a small amount of water, as well as the need to wash clothes in a short time to improve the efficiency of housework.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 59-6299
[0008] Patent Document 2: Japanese Patent Application Publication No. 63-305198
[0009] Patent Document 3: Japanese Patent Application Publication No. 11-5992
[0010] Patent Document 4: International Publication No. 2002 / 046348
[0011] Patent Document 5: Japanese Patent Application Publication No. 2022-080076 Summary of the Invention
[0012] The problem that the invention aims to solve
[0013] In order to meet the needs mentioned above, various additives for liquid laundry detergents have been developed in the past, but there is still room for further improvement in the dirt-cleaning performance of liquid laundry detergents.
[0014] In addition, as consumers become increasingly concerned about environmental protection, they hope to use additives derived from sustainable resources, such as biodegradable compounds.
[0015] The present invention was made in view of the above-mentioned situation, and its object is to provide a composition comprising a biodegradable additive that can exert excellent cleaning performance when used as a liquid laundry detergent.
[0016] Methods for solving problems
[0017] The inventors conducted various studies on detergent additives and found that, in a composition containing surfactants in a specified proportion, by adding a ethylene alcohol polymer with a specified amount of cationic surfactant and inorganic detergent builder in a specified proportion, which is biodegradable and has an average degree of polymerization within a specified range, it exhibits excellent cleaning performance when used as a liquid laundry detergent. The inventors also realized that it could perfectly solve the above-mentioned problems, and thus completed the present invention.
[0018] The present invention includes the following liquid laundry detergent compositions, etc.
[0019] [1] A liquid laundry detergent composition comprising a vinyl alcohol polymer and a surfactant, wherein the vinyl alcohol polymer has a structural unit (a) as shown in formula (1), and optionally has a structural unit (b) as shown in formula (2), and other structural units (c) besides the structural unit (a) and the structural unit (b). [Chemical Formula 1]
[0020] [Chemical Formula 2]
[0021] Relative to the total amount of all structural units (100 mol%), the content ratio of each structural unit is structural unit (a) / structural unit (b) / other structural units (c) = 50~100 / 0~50 / 0~20 mol%, the average degree of polymerization is 50~800, the content ratio of the vinyl alcohol polymer is 0.3~10% by mass relative to 100% by mass of the liquid laundry detergent composition, the content ratio of the surfactant is 10~80% by mass relative to 100% by mass of the surfactant, the proportion of cationic surfactant is less than 20% by mass relative to 100% by mass of the liquid laundry detergent composition, and the content ratio of inorganic detergent builder is less than 50% by mass relative to 100% by mass of the liquid laundry detergent composition.
[0022] [2] According to the liquid laundry detergent composition described in [1] above, the probability of compatibility 1 / (1+Exp(-y)) represented by y as specified in the following formula (I) is 0.5 or more.
[0023] y=73.7-0.418×α-0.725×β-0.00332×γ (I)
[0024] (In the formula, α represents the proportion (mass%) of surfactant in the evaluation solution when evaluating compatibility with liquid laundry detergent compositions. β represents the degree of saponification of the vinyl alcohol polymer (mol%). γ represents the average degree of polymerization of the vinyl alcohol polymer.)
[0025] [3] According to the liquid laundry detergent composition described in [1] or [2] above, the content of the surfactant is 45 to 80% by mass relative to 100% by mass of the liquid laundry detergent composition.
[0026] [4] The liquid laundry detergent composition according to any one of [1] to [3] above, wherein the surfactant comprises anionic surfactant.
[0027] [5] The liquid laundry detergent composition according to any one of [1] to [4] above, wherein the surfactant comprises anionic surfactant and nonionic surfactant.
[0028] [6] The liquid laundry detergent composition according to any one of [1] to [5] above, wherein the surfactant comprises anionic surfactant and nonionic surfactant, and the proportion of anionic surfactant is 30% or more relative to 100% by mass of the total anionic surfactant and nonionic surfactant.
[0029] [7] The liquid laundry detergent composition according to [5] or [6] above, wherein the proportion of nonionic surfactant is 5 to 70% by mass relative to 100% by mass of total surfactant.
[0030] [8] The liquid laundry detergent composition according to any one of [1] to [7] above, wherein the liquid laundry detergent composition comprises a polyalkylene glycol compound.
[0031] [9] According to the liquid laundry detergent composition described above [8], the content of the above polyalkylene glycol compound is 100 to 1000% by mass relative to 100% by mass of the vinyl alcohol polymer.
[0032]
[10] The liquid laundry detergent composition according to any one of [1] to [9] above, wherein the liquid laundry detergent composition contains an enzyme.
[0033]
[11] A composite composition containing a liquid laundry detergent composition encapsulated in a detergent packaging film, wherein the liquid laundry detergent composition comprises a vinyl alcohol polymer and a surfactant, the vinyl alcohol polymer having a structural unit (a) as shown in formula (1), and optionally having a structural unit (b) as shown in formula (2), and other structural units (c) besides the structural unit (a) and the structural unit (b). [Chemical Formula 3]
[0034] [Chemical Formula 4]
[0035] Relative to the total amount of all structural units (100 mol%), the content ratio of each structural unit is structural unit (a) / structural unit (b) / other structural units (c) = 50~100 / 0~50 / 0~20 mol%, and the average degree of polymerization is 50~800.
[0036]
[12] According to the composite composition described above
[11] , the surfactant is contained in a proportion of 50 to 80% by mass relative to 100% by mass of the liquid laundry detergent composition.
[0037] Invention Effects
[0038] The liquid laundry detergent composition of the present invention comprises the above-described structure and contains biodegradable additives, exhibiting excellent cleaning performance when used as a liquid laundry detergent, and is therefore suitable for use in concentrated liquid laundry detergents, etc. Detailed Implementation
[0039] The preferred embodiments of the present invention will be specifically described below, but the present invention is not limited to the following description, and appropriate modifications can be made without changing the spirit of the invention. Furthermore, combinations of two or more of the preferred embodiments described below are also preferred embodiments of the present invention.
[0040] [Liquid laundry detergent composition]
[0041] The liquid laundry detergent composition of the present invention comprises a vinyl alcohol polymer and a surfactant. The vinyl alcohol polymer has a structural unit (a) shown in formula (1) above, and may further have a structural unit (b) shown in formula (2) above, and other structural units (c) other than the structural units (a) and (b) above. The content ratio of each structural unit relative to the total amount of all structural units is structural unit (a) / structural unit (b) / other structural units (c) = 50-100 / 0-50 / 0-20 mol%, the average degree of polymerization is 50-800, and the content ratio of the surfactant is 10-80% by mass relative to 100% by mass of the liquid laundry detergent composition.
[0042] The liquid laundry detergent composition of the present invention, having the above-described structure, exhibits excellent cleaning performance when used as a liquid laundry detergent, and also demonstrates excellent biodegradability. The liquid laundry detergent composition of the present invention exhibits particularly excellent cleaning performance against dirt and grime.
[0043] The surfactant content in the above-mentioned liquid laundry detergent composition is 10-80% by mass relative to 100% by mass of the liquid laundry detergent composition, preferably 15-80% by mass. It is believed that in this case, the interaction between the surfactant and the vinyl alcohol polymer becomes stronger, which can further improve the effect of the surfactant.
[0044] The surfactant content is more preferably 15-75% by mass, further preferably 20-75% by mass, and particularly preferably 20-70% by mass. In one embodiment, the surfactant content is 30-80%, 40-80%, or 45-80% by mass relative to 100% by mass of the liquid laundry detergent composition.
[0045] The surfactants mentioned above preferably include anionic surfactants, and the proportion is not particularly limited. It is preferably 30% by mass or more relative to 100% by mass of the total surfactant content in the liquid laundry detergent composition. More preferably, it is 40-100% by mass, even more preferably 40-90% by mass, and particularly preferably 50-90% by mass.
[0046] In one embodiment, the proportion of anionic surfactant relative to 100% by mass of the total surfactant is preferably 5% by mass or more. More preferably, it is 10-90% by mass, and even more preferably 20-80% by mass.
[0047] The surfactants mentioned above preferably include nonionic surfactants, and their proportions are not particularly limited. The proportion is preferably 0-70% by mass relative to 100% of the total surfactant content in the liquid laundry detergent composition. More preferably, it is 0-60% by mass, even more preferably 10-60% by mass, and particularly preferably 10-50% by mass.
[0048] In one embodiment, it is also preferred that the proportion of the aforementioned nonionic surfactant is 5 to 50% by mass relative to 100% of the total surfactant amount. More preferably, it is 7.5 to 40% by mass, and even more preferably, it is 10 to 30% by mass.
[0049] The surfactants mentioned above preferably include anionic surfactants and nonionic surfactants. The total ratio of anionic surfactants to nonionic surfactants is not particularly limited, but is preferably 15 to 80% by mass relative to 100% of the total surfactant content in the liquid laundry detergent composition. More preferably, it is 15 to 75% by mass, even more preferably 20 to 75% by mass, and particularly preferably 20 to 70% by mass.
[0050] The aforementioned surfactant may contain a cationic surfactant, and its proportion is 20% by mass or less relative to 100% by mass of the total surfactant in the liquid laundry detergent composition. This sufficiently suppresses any resistance to the cleaning performance of the aforementioned anionic surfactant. The proportion of the cationic surfactant is preferably 15% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and most preferably 0% by mass.
[0051] Of the surfactants mentioned above, the proportion of anionic surfactants relative to 100% by mass of the total anionic and nonionic surfactants is not particularly limited, but is preferably 30% by mass or more. More preferably, it is 40 to 100% by mass, even more preferably 40 to 90% by mass, and particularly preferably 50 to 90% by mass.
[0052] The proportion of the vinyl alcohol polymer in the above-mentioned liquid laundry detergent composition is not particularly limited, but is preferably 0.5 to 10% by mass relative to 100% by mass of the liquid laundry detergent composition. More preferably, it is 1 to 9% by mass, and even more preferably, it is 2 to 8% by mass.
[0053] In one embodiment, it is also preferred that the proportion of the above-mentioned vinyl alcohol polymer is 0.3 to 10% by mass relative to 100% by mass of the liquid laundry detergent composition. More preferably, it is 0.5 to 8% by mass, and even more preferably, it is 0.8 to 6% by mass.
[0054] Furthermore, the content of the vinyl alcohol polymer in the above-mentioned liquid laundry detergent composition is preferably 0.1 to 30% by mass relative to 100% by mass of the surfactant. More preferably, it is 1 to 20% by mass, even more preferably 2 to 15% by mass, and particularly preferably 3 to 10% by mass.
[0055] The above-mentioned liquid laundry detergent composition may contain other components besides vinyl alcohol polymers and surfactants. The proportion of other components is not particularly limited, but is preferably 10-90% by mass. More preferably, it is 20-85% by mass, and even more preferably, it is 30-80% by mass.
[0056] From the viewpoint of improving cleanliness and stability of the composition, the pH of the above-mentioned liquid laundry detergent composition at 25°C is preferably 5 to 11. More preferably, it is 5.5 to 10.5; even more preferably, it is 6 to 10; still more preferably, it is 6 to 9.5; and particularly preferably, it is 6 to 9. This pH is a value measured using a glass electrode at 25°C. Specifically, it is measured by the following method.
[0057] (Methods for pH measurement)
[0058] The pH electrode (model 6367) of the Horiba Manufacturing D-52 pH meter was calibrated beforehand using phthalic acid buffer (pH 4.01), phosphate standard solution (pH 6.84), and borate standard solution (pH 9.18), and then thoroughly rinsed with deionized water. The calibrated and cleaned pH electrode was placed in a liquid laundry detergent composition at 25°C, and the pH meter was measured in AUTO HOLD mode until the measured value remained constant.
[0059] The probability of compatibility 1 / (1+Exp(-y)) of the liquid laundry detergent composition described above is preferably 0.5 or more, as specified in the following formula (I).
[0060] y=73.7-0.418×α-0.725×β-0.00332×γ (I)
[0061] (In the formula, α represents the proportion (mass%) of surfactant in the evaluation solution when evaluating compatibility with liquid laundry detergent compositions. β represents the degree of saponification of the vinyl alcohol polymer (mol%). γ represents the average degree of polymerization of the vinyl alcohol polymer.)
[0062] Equation (I) above is a formula for binarizing the compatibility or incompatibility of a composition by changing the surfactant concentration, saponification degree and average degree of polymerization of the vinyl alcohol polymer in the compatibility evaluation solution, and then parameterizing it by logistic regression.
[0063] The above-described liquid laundry detergent composition preferably contains a polyalkylene glycol compound. This improves the compatibility of the composition with surfactants.
[0064] The proportion of polyalkylene glycol compounds in the above-mentioned liquid laundry detergent composition is not particularly limited, but is preferably 100 to 1000% by mass relative to 100% by mass of the vinyl alcohol polymer. More preferably, it is 100 to 900% by mass, and even more preferably, it is 100 to 800% by mass.
[0065] The liquid laundry detergent composition of the present invention may contain inorganic detergent builders, which are 50% by mass or less relative to 100% by mass of the liquid laundry detergent composition. This prevents the separation of inorganic components from the composition and the resulting instability.
[0066] The proportion of inorganic detergent additive is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, and most preferably 0% by mass.
[0067] There are no particular restrictions on inorganic detergent builders; examples include sodium carbonate, sodium tripolyphosphate, potassium pyrophosphate, sodium silicate, sodium sulfate, and zeolite.
[0068] The liquid laundry detergent composition of the present invention preferably contains water. The water can be ion-exchanged water, distilled water, tap water, or water containing 1 mg / kg to 5 mg / kg of sodium hypochlorite. From the viewpoint of the composition's viscosity and other physical properties, and its operability during laundry, the water content of the liquid laundry detergent composition of the present invention is preferably 5-90% by mass, more preferably 5-85% by mass, further preferably 5-80% by mass, and particularly preferably 5-75% by mass, relative to 100% by mass of the composition. In one embodiment, a water content of 10-70% by mass, 20-65% by mass, or 30-60% by mass relative to 100% by mass of the liquid laundry detergent composition is also a preferred embodiment.
[0069] The essential and optional ingredients contained in the liquid laundry detergent composition of the present invention will be further described below.
[0070] <Vinyl Alcohol-based Polymers>
[0071] The liquid laundry detergent composition of the present invention contains a vinyl alcohol polymer having a structural unit (a) as shown in formula (1) above, and may further have a structural unit (b) as shown in formula (2) above, and other structural units (c) besides the above structural units (a) and (b) above. The content ratio of each structural unit relative to the total amount of all structural units is 100 mol% as structural unit (a) / structural unit (b) / other structural units (c) = 50~100 / 0~50 / 0~20 mol%, and the average degree of polymerization is 50~800.
[0072] The proportion of structural unit (a) in the above-mentioned vinyl alcohol polymer relative to the total amount of all structural units (100 mol%) is preferably 50-100 mol%, more preferably 55-100 mol%, even more preferably 60-100 mol%, and particularly preferably 65-99 mol%, especially preferably 70-98 mol%. In one embodiment, a proportion of structural unit (a) of 5-100 mol% or 80-100 mol% relative to the total amount of all structural units (100 mol%) is also a preferred embodiment.
[0073] In one embodiment, the proportion of structural unit (a) relative to the total amount of all structural units (100 mol%) is preferably 50 to 95 mol%. This results in superior cleaning power for hydrophobic dirt such as sebum, as well as complex dirt composed of hydrophilic and hydrophobic dirt. More preferably, it is 60 to 90 mol%, and even more preferably, it is 70 to 90 mol%.
[0074] The proportion of structural unit (b) in the above-mentioned vinyl alcohol polymer relative to the total amount of all structural units (100 mol%) is 0 to 50 mol%, preferably 0 to 45 mol%, more preferably 0 to 40 mol%, even more preferably 0 to 35 mol%, and particularly preferably 0 to 30 mol%. In one embodiment, the proportion of structural unit (b) relative to the total amount of all structural units (100 mol%) is 0.1 to 25 mol%, or 1 to 20 mol%, which is also a preferred embodiment.
[0075] The proportion of structural unit (c) in the above-mentioned vinyl alcohol polymer relative to the total amount of all structural units (100 mol%) is 0 to 20 mol%, preferably 0 to 15 mol%, more preferably 0 to 10 mol%, further preferably 0 to 5 mol%, and particularly preferably 0 to 1 mol%. The proportion of structural unit (c) being 0 mol% is also one of the preferred embodiments of the present invention.
[0076] The aforementioned vinyl alcohol polymer may have structural units derived from the hydrophobic monomers described later as structural unit (c), and the proportion of such units is not particularly limited, but is preferably 10 mol% or less relative to the total amount of all structural units (100 mol%). More preferably, it is 10 mol% or less, further preferably 5 mol% or less, particularly preferably 1 mol% or less, and most preferably 0 mol%.
[0077] The above-mentioned vinyl alcohol polymers may have structural units derived from alkyl-substituted 1-ene monomers described later, with a total structural unit percentage of 100 mol%, preferably less than 0.25 mol%, more preferably 0 mol%, relative to the total amount of all structural units.
[0078] The average degree of polymerization of the above-mentioned vinyl alcohol-based polymers is 50 to 800. Therefore, the liquid laundry detergent composition of the present invention can exhibit excellent cleaning performance. As for the average degree of polymerization, 50 to 700 is preferred, more preferably 100 to 600, even more preferably 100 to 500, and particularly preferably 100 to 450.
[0079] The average degree of polymerization described above can be determined using the methods described in the examples.
[0080] The above-mentioned vinyl alcohol polymers may have structural unit (c), and there are no particular restrictions on structural unit (c) as long as it is a structural unit other than structural unit (a) and structural unit (b).
[0081] As the monomer forming the above structural unit (c), any monomer that can copolymerize with vinyl acetate, which is the raw material for structural units (a) and (b), can be used. Examples include unsaturated alcohols with 3 to 8 carbon atoms, such as (meth)allyl alcohol and 3-methyl-3-buten-1-ol (isopentenol), and their esters with carboxylic acids with 2 to 8 carbon atoms; unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, fumaric acid, and citraconic acid, and their esters with alkoxy polyalkylene glycols such as methoxy polyethylene glycol; epoxide adducts obtained by adding unsaturated alcohols such as allyl alcohol and isopentenol to ethylene oxide, propylene oxide, etc.; acrylamide, sodium acrylamide propanesulfonate, sodium 2-hydroxy-3-allyloxypropanesulfonate, hydroxyethyl acrylate, hydroxyethyl methacrylate, ethylene glycol, etc. Vinyl ethers such as monovinyl alcohol ethers, diethylene glycol monovinyl ethers, and hydroxybutyl vinyl ethers; alkyl esters of ethylene oxide and propylene oxide; methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate; alkyl methacrylates such as styrene; aromatic vinyl monomers such as ethylene, propylene, and alkyl-substituted 1-ene monomers; alkyl vinyl ethers such as methyl vinyl ethers and ethyl vinyl ethers; cyclic vinyl monomers such as N-vinylpyrrolidone; acrylonitrile; vinyl formamide and vinyl acetamide. Among the monomers forming structural unit (c) above, esters of unsaturated alcohols with 3 to 8 carbon atoms and carboxylic acids with 2 to 8 carbon atoms; esters of unsaturated carboxylic acids and alkoxy polyalkylene glycols; alkyl esters of (meth)acrylates; aromatic vinyl monomers; olefin monomers, etc., are hydrophobic monomers, and these monomers are preferably used in the above proportions.
[0082] There are no particular limitations on the form of the above-mentioned vinyl alcohol polymers. They can be dissolved in the composition or form a film, such as microcapsules. The dissolved form is preferred.
[0083] In one embodiment, the liquid laundry detergent composition of the present invention preferably does not contain the above-mentioned vinyl alcohol polymer in the form of macrocapsules.
[0084] [Preparation method of vinyl alcohol polymers]
[0085] There are no particular limitations on the manufacturing method of the above-mentioned vinyl alcohol polymer. When the above-mentioned vinyl alcohol polymer is a polymer consisting only of structural unit (a) or composed of structural units (a) and (b), it is preferable to manufacture it by polymerizing vinyl acetate and then hydrolyzing it.
[0086] In addition, when the above-mentioned vinyl alcohol polymer has structural unit (c), it is preferable to manufacture it by copolymerizing vinyl acetate with the monomer that forms structural unit (c) and then hydrolyzing it.
[0087] The polymerization temperature of the monomer components in the manufacture of the above-mentioned vinyl alcohol polymers is preferably 0–70°C. More preferably, it is 10–70°C, even more preferably 20–70°C, and particularly preferably 30–70°C.
[0088] In the above polymerization reaction, a polymerization initiator is preferably used.
[0089] As polymerization initiators, low-temperature decomposition free radical initiators such as diisopropyl peroxide, isobutyryl peroxide, 2,2'-azobis(4-methoxy-2,4-dimethylpentanonitrile), bis(4-tert-butylcyclohexyl) peroxide, dimyristyl peroxide, acetylcyclohexylsulfonyl peroxide, n-propyl peroxide, α-cumyl peroxide neodecanoate, and 2,4,4-triethylpentyl peroxide phenoxyacetate can be used effectively, but are not limited to these. Additionally, initiators such as 2,2'-azobisisobutyronitrile can be used in combination with ultraviolet irradiation. Furthermore, redox initiator systems composed of peroxide-based free radical initiators combined with reducing agents such as dimethylaniline and α-ascorbic acid, and oxidizing agents such as iron salts are also effective. Furthermore, free radical polymerization initiated by electron beams or radiation is also effective.
[0090] In the above polymerization reaction, chain transfer agents can be used.
[0091] Thiols such as mercaptoethanol, thioglycerol, thioglycolic acid, 3-mercaptopropionic acid, thiomalic acid, and 2-mercaptoethanesulfonic acid can be used as chain transfer agents.
[0092] There are no particular restrictions on the method of adding the above-mentioned thiols. A specified amount can be added to the polymerization system before polymerization is initiated, and the above-mentioned thiols can be continuously supplied to the polymerization system at a certain rate after the polymerization has substantially started.
[0093] The above-mentioned vinyl alcohol-based polymers preferably begin the saponification of polyvinyl acetate in an alcohol containing a base catalyst of a specified concentration or higher. When the alcohol is methanol, it is preferable that at least the initial stage of the polyvinyl acetate saponification reaction is carried out in methanol containing a base catalyst of 0.18 mol / L or higher.
[0094] There are no particular limitations on the alkaline catalyst used in the above saponification reaction, but alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred. Sodium hydroxide is more preferred.
[0095] <surfactants>
[0096] The surfactant contained in the liquid laundry detergent composition of the present invention is not particularly limited as long as it has surface-active properties; examples include anionic surfactants, nonionic surfactants, and cationic surfactants. Among them, anionic surfactants and nonionic surfactants are preferred.
[0097] One preferred embodiment of the present invention comprises anionic and nonionic surfactants in its liquid laundry detergent composition. In this case, the liquid laundry detergent composition of the present invention can exhibit superior cleaning performance.
[0098] (Anionic surfactant)
[0099] There are no particular restrictions on the above-mentioned anionic surfactants as long as they have a hydrophobic group and a hydrophilic group that dissociates into anion. For example, the structure shown in the following formula (3) is preferred.
[0100] R 1 -(O) m -(A 1 O) n1 -W
[0101] (where R is in the formula) 1 Same or different, indicating hydrocarbon groups with 6 to 24 carbon atoms; A 1 The presence or absence of 'O' indicates an oxoalkylene group with 2 to 18 carbon atoms; 'n1' indicates A. 1 The average molar number of oxyalkylene groups represented by O is an integer from 0 to 50; m is 0 or 1; W represents a hydrophilic group that dissociates into an anion.
[0102] The above A 1 The oxo group may be the same or different, and is an oxoalkylene group with 2 to 18 carbon atoms. The number of carbon atoms in the oxoalkylene group is preferably 2 to 8, and more preferably 2 to 4.
[0103] These alkylene oxides are alkylene oxide adducts, and specific examples of alkylene oxides are as described above, preferably ethylene oxide, propylene oxide, and butane oxide, and more preferably ethylene oxide and propylene oxide.
[0104] Furthermore, when the aforementioned alkylene oxide is selected from any two or more alkylene oxide adducts chosen from ethylene oxide, propylene oxide, butane oxide, styrene oxide, etc., it can be in any form such as random addition, block addition, or alternating addition. It should be noted that, to ensure a balance between hydrophilicity and hydrophobicity, the alkylene oxide in the polyalkylene glycol preferably contains ethylene oxide as an essential component, more preferably 50 mol% or more of ethylene oxide, even more preferably 80 mol% or more of ethylene oxide, and particularly preferably 90 mol% or more of ethylene oxide.
[0105] The n1 mentioned above can be 0 to 50, preferably 0 to 40, and even more preferably 0 to 30.
[0106] R 1 There are no particular restrictions on the hydrocarbon group; examples include alkyl, alkenyl, aryl, and aralkyl groups. Alkyl and alkenyl groups can be straight-chain or branched.
[0107] Examples of alkyl groups mentioned above include n-hexyl, isohexyl, secondary hexyl, tert-hexyl, neohexyl, 2-ethylhexyl, n-heptyl, isoheptyl, secondary hexyl, tert-heptyl, neoheptyl, n-octyl, isooctyl, secondary octyl, tert-octyl, neooctyl, n-nonyl, isononyl, secondary nonyl, tert-nonyl, neononyl, n-decyl, isodel, secondary decyl, tert-decyl, neodecyl, n-undecyl, isoundecyl, secondary undecyl, tert-undecyl, neoundecyl, n-dodecyl, isododecyl, secondary dodecyl, tert-dodecyl, neododecyl, n-tridecyl, isotridecyl, secondary tridecyl, tert-tridecyl, neotridecyl. Tetradecyl, isotetradecyl, tert-tetradecyl, neotetradecyl, pentadecyl, isopentadecanyl, tert-pentadecanyl, neopentadecanyl, hexadecyl, isohexadecyl, tert-hexadecyl, neohexadecyl, heptadecanyl, isoheptadecanyl, tert-hexadecyl, neohexadecyl, heptadecanyl, isoheptadecanyl, tert-heptadecanyl, neoheptadecanyl, octadecyl, isoheptadecanyl, tert-heptadecanyl, neoheptadecanyl, octadecyl, isoheptadecanyl, tert-heptadecanyl, neoheptadecanyl, nonadecanyl, isoheptadecanyl, tert-heptadecanyl, neoheptadecanyl, icosyl, isoicosyl, tert-icosyl, neoicosyl, etc.
[0108] Examples of alkenyl groups mentioned above include hexenyl, heptenyl, octenyl, nonenyl, decenyl, dodecenyl, octadecenyl, and eicoseneyl.
[0109] Examples of aryl groups include phenyl, methylphenyl, 1-methoxy-4-methylphenyl, ethylphenyl, propylphenyl, butylphenyl, butylmethylphenyl, dimethylphenyl, diethylphenyl, dibutylphenyl, biphenyl, naphthyl, etc.
[0110] Examples of aryl alkyl groups include benzyl, phenethyl, phenylpropyl, diphenylmethyl, biphenylmethyl, biphenylethyl, naphthylmethyl, and naphthylethyl.
[0111] R 1 The hydrocarbon group in the hydrocarbon group has 6 to 24 carbon atoms, preferably 6 to 22, more preferably 8 to 20, and even more preferably 8 to 18.
[0112] There are no particular restrictions on the hydrophilic group in W that dissociates into an anion; examples include sulfate (salt) groups, sulfonic acid (salt) groups, carboxylic acid (salt) groups, and phosphate (salt) groups. Sulfate (salt) groups, sulfonate (salt) groups, and carboxylic acid (salt) groups are preferred.
[0113] Examples of anionic surfactants include alkyl or alkenyl sulfate salts; polyoxyalkylene alkyl or alkenyl ether sulfate salts having oxyalkylene groups; anionic surfactants having sulfonate groups; fatty acids or their salts, etc.
[0114] More specifically, examples of the aforementioned alkyl or alkenyl sulfate salts include alkyl sulfate salts having 10 to 18 carbon atoms in the alkyl group and alkenyl sulfate salts having 10 to 18 carbon atoms in the alkenyl group.
[0115] More specifically, examples of polyoxyalkylene alkylene or alkenyl ether sulfates having an alkylene group include polyoxyalkylene alkylene ether sulfates with an alkyl group having 10 to 18 carbon atoms and an average molar number of alkylene oxide addition of 1 to 5; and polyoxyalkylene alkenyl ether sulfates with an alkenyl group having 10 to 18 carbon atoms and an average molar number of alkylene oxide addition of 1 to 5. Among these, polyoxyalkylene alkylene ether sulfates with an average molar number of ethylene oxide addition of 1 to 3 are preferred, polyoxyalkylene alkylene ether sulfates with an alkyl group having 12 to 14 carbon atoms and an average molar number of ethylene oxide addition of 1 to 3 are more preferred, and their sodium salts are even more preferred.
[0116] More specifically, examples of anionic surfactants having sulfonate groups include alkylbenzene sulfonates with 10 to 18 carbon atoms in the alkyl group, alkenylbenzene sulfonates with 10 to 18 carbon atoms in the alkenyl group, alkane sulfonates with 10 to 18 carbon atoms in the alkyl group, α-olefin sulfonates with 10 to 18 carbon atoms in the α-olefin moiety, α-sulfonyl fatty acid salts with 10 to 18 carbon atoms in the fatty acid moiety, lower alkyl esters of α-sulfonyl fatty acids with 10 to 18 carbon atoms in the fatty acid moiety and 1 to 5 carbon atoms in the ester moiety, and endoolefin sulfonates with 12 to 16 carbon atoms. Alkylbenzene sulfonates with 11 to 16 carbon atoms in the alkyl group are preferred, and sodium alkylbenzene sulfonate with 11 to 16 carbon atoms in the alkyl group is more preferred.
[0117] Examples of the aforementioned fatty acids or their salts include fatty acids or their salts having 10 to 20 carbon atoms. The number of carbon atoms in the aforementioned fatty acids or their salts is preferably 12 to 18, more preferably 14 to 18.
[0118] (Nonionic surfactant)
[0119] There are no particular restrictions on the above-mentioned nonionic surfactants as long as they have hydrophobic groups and hydrophilic groups such as hydroxyl groups, ether groups, and ester groups that do not dissociate into ions. For example, the structures shown in formulas (4-1) and / or (4-2) below are preferred.
[0120] R 2 -O-(A 2 O) n2 -H (4-1)
[0121] R 3 -COO-(A 3 O) n3 -R 4 (4-2)
[0122] (where R is in the formula) 2 R 3 Same or different indicates hydrocarbon groups with 6 to 24 carbon atoms; R 4 Indicates an alkyl group having 1 to 3 hydrogen atoms or carbon atoms; A 2 O, A 3 The same or different 'O' indicates an oxoalkylene group with 2 to 18 carbon atoms; 'n2' indicates A. 2 The average molar number of oxyalkylene groups represented by O is an integer from 1 to 50; n3 represents A. 3 The average number of moles of oxyalkylene groups represented by O is an integer from 5 to 50.
[0123] The above R 2 R 3 There are no particular restrictions on the hydrocarbon group used; examples include alkyl, alkenyl, aryl, and aralkyl groups. Alkyl and alkenyl groups can be straight-chain or branched. Specific examples of alkyl, alkenyl, aryl, and aralkyl groups are as described above.
[0124] The above R 2 R 3 The hydrocarbon group in the hydrocarbon group has 6 to 24 carbon atoms, preferably 6 to 22, more preferably 8 to 20, and even more preferably 8 to 18.
[0125] The above A 2 O, A 3 Specific examples and preferred methods of O and A 1 O is the same.
[0126] The values of n2 and n3 are preferably 1 to 30, more preferably 1 to 22, even more preferably 2 to 18, and particularly preferably 3 to 16.
[0127] In the above formula (4-1), -(A 2 O) n2 -for-(EO) n2’ -(PO) n2”This method is one of the preferred embodiments of the present invention.
[0128] In the above formula, n2' is the average number of moles added to EO, which is a number from 1 to 20, preferably from 2 to 10. n2” is the average number of moles added to PO, which is a number from 1 to 20, preferably from 2 to 10.
[0129] Specifically, the aforementioned nonionic surfactant is preferably a compound formed by adding 1 to 50 moles of ethylene oxide (EO) and / or propylene oxide (PO) to an alkyl alcohol having 6 to 24 carbon atoms. The total molar number of EO and PO added is more preferably 2 to 30, further preferably 2 to 25, and particularly preferably 3 to 20.
[0130] The alkyl alcohols mentioned above can be straight-chain or branched, and the alkyl alcohols being primary or secondary alcohols is one of the preferred embodiments of the present invention.
[0131] In addition, the preferred embodiments of the present invention are the addition of ethylene oxide only to the alkyl alcohol and the sequential block addition of propylene oxide and ethylene oxide to the alkyl alcohol.
[0132] (Catonic surfactant)
[0133] As for the aforementioned cationic surfactants, there are no particular limitations as long as they have a hydrophobic group and a hydrophilic group that dissociates into a cation. For example, quaternary ammonium salt cationic surfactants can be cited.
[0134] Examples of quaternary ammonium salt-type cationic surfactants include quaternary ammonium salts in which one or two of the four groups bonded to the nitrogen atom are hydrocarbon groups with 6 to 24 carbon atoms, and the remainder are hydrocarbon groups with 1 to 3 carbon atoms. Compounds represented by the following formula (5) are preferred examples of cationic surfactants.
[0135] [Chemical Formula 5]
[0136] (where R is in the formula) 5 It is a chain hydrocarbon group with 8 to 24 carbon atoms, R 6 It is a chain hydrocarbon group with 8 to 24 carbon atoms, an alkyl group with 1 to 3 carbon atoms, or a hydroxyalkyl group with 1 to 3 carbon atoms, R 7 and R 8 Whether the carbon atoms are the same or different, the carbon atoms are alkyl groups with 1 to 3 carbon atoms or hydroxyalkyl groups with 1 to 3 carbon atoms, X - These are alkyl sulfate ions or halide ions with 1 to 3 carbon atoms.
[0137] In equation (5) above, R 5The chain-like hydrocarbon group preferably has 9 to 18 carbon atoms, more preferably 10 to 14, and even more preferably 10 to 12. 6 It is a chain hydrocarbon group with 8 to 24 carbon atoms, an alkyl group with 1 to 3 carbon atoms, or a hydroxyalkyl group with 1 to 3 carbon atoms, R 6 The chain hydrocarbon group preferably has 9 to 18 carbon atoms, more preferably 10 to 14, and even more preferably 10 to 12.
[0138] R 6 The chain-like hydrocarbon group is preferably alkyl or alkenyl, more preferably alkyl. 7 R 8 Whether the same or different, it is methyl, ethyl or hydroxyalkyl with 1 to 3 carbon atoms.
[0139] R 5 R 6 Specific examples of chain-like hydrocarbon groups include octyl, nonyl, decyl, dodecyl, tetradecyl, and hexadecyl, with nonyl and decyl being preferred, and decyl being even more preferred. Specific examples of hydroxyalkyl groups with 1 to 3 carbon atoms include hydroxymethyl, hydroxyethyl, and hydroxypropyl.
[0140] X - CH3SO4 - CH3CH2SO4 - Or halide ions.
[0141] More specific compounds representing the compounds in formula (5) above may be selected from one or more of N-ethyl-N,N-dimethyltetradecylammonium salt, trimethylhexadecylammonium salt, N,N-dioctyl-N,N-dimethylammonium salt, N,N-dinonyl-N,N-dimethylammonium salt, N,N-didecyl-N,N-dimethylammonium salt, N,N-dioctyl-N-ethyl-N-methylammonium salt, N,N-dinonyl-N-ethyl-N-methylammonium salt, and N,N-didecyl-N-ethyl-N-methylammonium salt. Single-chain and double-chain ammonium salts may also be used in combination. N,N-didecyl-N-ethyl-N-methylammonium salt is preferred.
[0142] The counter ion of these salts is CH3SO4. - CH3CH2SO4 - Or halide ions such as chloride ions.
[0143] The content of the above-mentioned cationic surfactant is not particularly limited, and is preferably 0 to 50% by mass relative to 100% by mass of the composition, more preferably 0 to 40% by mass, and even more preferably 0 to 30% by mass.
[0144] <Polyalkylene glycol compounds>
[0145] The above-mentioned liquid laundry detergent composition preferably contains a polyalkylene glycol compound. This results in better compatibility between the composition and surfactants.
[0146] There are no particular restrictions on the aforementioned polyalkylene glycol compounds as long as they contain polyoxyalkylene groups. Examples include: diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, etc., which contain alkylene glycol units with 2 to 4 carbon atoms; monoalkyl ethers of polyalkylene glycols containing alkylene glycol units with 2 to 4 carbon atoms and alkyl groups with 1 to 4 carbon atoms, such as diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.; aromatic alkyl ethers of polyalkylene glycols containing alkylene glycol units with 2 to 3 carbon atoms, such as diethylene glycol monophenyl ether, triethylene glycol monophenyl ether, polyethylene glycol monophenyl ether with an average molecular weight of approximately 480, diethylene glycol monobenzyl ether, etc.; and epoxy alkyl adducts of polyalkylene imides such as polyethyleneimine.
[0147] The average molar number of oxyalkylene groups added in the above-mentioned polyalkylene glycol compounds is not particularly limited, but is preferably 2 to 500. More preferably, it is 10 to 400, even more preferably 20 to 300, even more preferably 30 to 250, even more preferably 40 to 200, and particularly preferably 50 to 150.
[0148] When the above-mentioned polyalkylene glycol compound is an alkylene oxide adduct of polyalkylene imine, the ratio of alkylene oxide to 1 mole of nitrogen atom is preferably 1 to 100 moles. More preferably, it is 5 to 50, and even more preferably, it is 10 to 30.
[0149] When the aforementioned polyalkylene glycol compound is an epoxy alkylene imide adduct, the number average molecular weight of the polyalkylene imide is not particularly limited, but is preferably 100 to 100,000. More preferably, it is 200 to 50,000; even more preferably, it is 300 to 10,000; even more preferably, it is 400 to 5,000; and even more preferably, it is 500 to 3,000.
[0150] <Other Ingredients>
[0151] The above-described liquid laundry detergent composition may contain other ingredients besides vinyl alcohol polymers and surfactants. There are no particular limitations on other ingredients, and for example, the ingredients listed in (1) to (11) below can be cited.
[0152] (1) Enzymes
[0153] From the viewpoint of cleaning power against various types of dirt adhering to clothing, the liquid laundry detergent composition of the present invention preferably contains enzymes.
[0154] As an enzyme, there are no particular restrictions as long as it breaks down the components of dirt. Examples include glycolytic enzymes, proteolytic enzymes, lipolytic enzymes, oxidoreductases, and other degrading enzymes. They can be used alone or in combination of two or more.
[0155] Examples of saccharifying enzymes include amylase, sucrase, maltase, lactase, amylopectinase, fructofuranosidase, cellulase, hemicellulase, xylanase, pectinase, pentosanase, mannanase, β-glucanase, and arabinosidase. From the viewpoint of improving cleanliness and maintaining cleanliness after storage, amylase is preferred, and α-amylase is more preferred. Examples of commercially available enzymes include Rapidase (manufactured by Gist Brocades), Termamyl, Duramyl, Stainzyme, and Amplify Prime 100L (manufactured by Novozymes Japan KK), Purastar ST and Purastar OxAm (manufactured by Genencor International), and Preference S210 (manufactured by DuPont KK).
[0156] There are no particular limitations on the protein-degrading enzymes mentioned above; examples include pepsin, trypsin, peptidase, and other proteases.
[0157] Examples of fat-decomposing enzymes include lipases, phospholipases, and lipoxygenases.
[0158] There are no particular limitations on the types of oxidoreductases mentioned above; examples include peroxidases, reductases, oxidases, phenol oxidases, and laccases.
[0159] Other decomposing enzymes mentioned above are not particularly limited and can include esterases, keratinases, ligninases, tanninases, hyaluronidases, chondroitinases, etc.
[0160] From the viewpoint of achieving higher cleaning performance for stains such as meat sauce and other food residues on clothing with sebum, an enzyme containing protease is preferred.
[0161] The content of the above-mentioned enzyme is not particularly limited, but is preferably 0.01 to 3% by mass relative to 100% by mass of the liquid laundry detergent composition. More preferably, it is 0.05 to 2% by mass, and even more preferably, it is 0.1 to 1% by mass.
[0162] (2) Alkali
[0163] From the viewpoint of improving cleaning power, the liquid laundry detergent composition of the present invention preferably contains an alkaline agent. Examples of alkaline agents include inorganic alkaline agents such as alkali metal hydroxides and alkali metal carbonates; and alkanolamines in which one to three of the groups bonded to the nitrogen atom are alkyl groups having two to four carbon atoms, with the remainder being alkyl groups having one to four carbon atoms or hydrogen atoms. The alkyl groups are preferably hydroxyalkyl, and more preferably hydroxyethyl. The groups other than the alkyl groups are preferably hydrogen atoms or methyl groups, and particularly preferably hydrogen atoms. Examples of alkanolamines include 2-aminoethanol, N-methylethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, diethanolamine, N-methyldiethanolamine, and triethanolamine. In the present invention, as component (2), an alkanolamine selected from monoethanolamine and triethanolamine is preferred, and monoethanolamine is more preferred.
[0164] In addition, the alkali agent, which is the component of (2) above, can also be used to adjust the pH of the liquid laundry detergent composition of the present invention to a specified value.
[0165] In the liquid laundry detergent composition of the present invention, component (2) may be incorporated in an amount that achieves the aforementioned pH. The amount of component (2) incorporated is preferably 0.01 to 10% by mass, more preferably 0.5 to 8% by mass, relative to 100% of the composition. It should be noted that in the present invention, the amount of the alkali agent, especially the alkanolamine, in component (2) includes the portion derived from other components such as the counterion of anionic surfactants that are incorporated into the composition.
[0166] (3) Chelating agents
[0167] Specific examples of the chelating agents mentioned above include aminopolyacetic acids such as ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, and hydroxyethyliminodiacetic acid, or their salts; organic acids such as citric acid, lactic acid, tartaric acid, and malic acid, or their salts; 1-hydroxyethylidene-1,1-diphosphonic acid; diethylenetriaminepenta (methylenephosphonic acid); their alkali metal salts or lower amine salts; and hypozinotriacetic acid salts. (3) The content of the chelating agent in the component, when calculated as acidic, is preferably 0.1% to 5% by mass relative to 100% by mass of the composition, more preferably 0.1% to 4% by mass, and even more preferably 0.1% to 3% by mass.
[0168] The liquid laundry detergent composition of the present invention may contain hypotriacetate, but it is preferable to exclude it from the present invention in a weight ratio (ethylene alcohol polymer / hypotriacetate) of 0.1 to 2. As for the proportion of hypotriacetate to 100% by mass of the ethylene alcohol polymer in the above-mentioned liquid laundry detergent composition, it is preferably 33% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, particularly preferably 10% by mass or less, and most preferably 0% by mass.
[0169] (4) Anti-recontamination agents and / or polymeric dispersants
[0170] Examples of anti-recontamination agents and / or polymeric dispersants include polyacrylic acid, polymaleic acid, and carboxymethyl cellulose. The content of the anti-recontamination agent and / or polymeric dispersant relative to 100% by mass of the composition is preferably 0.01% by mass or more and 10% by mass or less.
[0171] (5) Bleach
[0172] Examples of bleaching agents include hydrogen peroxide, sodium percarbonate, and sodium perborate. The content of the bleaching agent relative to 100% by mass of the composition is preferably 0.01% by mass or more and 10% by mass or less.
[0173] (6) Bleaching activator
[0174] Examples of bleaching activators include tetraacetylethylenediamine and bleaching activators with general formulas (I-2) to (I-7) disclosed in Japanese Patent Application Publication No. 6-316700. The content of the bleaching activator is preferably 0.01% to 10% by mass relative to 100% by mass of the composition.
[0175] (7) Fluorescent dyes
[0176] Examples of fluorescent dyes include commercially available fluorescent dyes such as Tinopal CBS (trade name, manufactured by Ciba Specialty Chemicals) and Whitex SA (trade name, manufactured by Sumitomo Chemicals). The content of the fluorescent dye relative to 100% by mass of the composition is preferably 0.001% by mass or more and 1% by mass or less.
[0177] (8) Antioxidants
[0178] Examples of antioxidants include butylated hydroxytoluene, stilbene cresol, sodium sulfite, and sodium bisulfite. The antioxidant content is preferably 0.01% by mass or more and 2% by mass or less relative to 100% by mass of the composition.
[0179] (9) Preferably, an appropriate amount of defoamer containing pigments, fragrances, antibacterial preservatives, organosilicon and other ingredients is selected.
[0180] (10) Organic solvents containing hydroxyl groups
[0181] As an organic solvent containing hydroxyl groups, one or more compounds selected from the following components (10-1) to (10-5) can be used.
[0182] (10-1) Composition: Monohydric alcohols with 2 to 6 carbon atoms in aliphatic hydrocarbon groups.
[0183] As a component of (10-1), examples include monohydric alcohols selected from ethanol, 1-propanol, 2-propanol and 1-butanol.
[0184] (10-2) Composition: Alcohols with 2 to 6 carbon atoms, consisting of two to 6 carbon atoms, or 6 carbon atoms.
[0185] As a component (10-2), examples include diols or triols selected from ethylene glycol, propylene glycol, butylene glycol, 2-methyl-2,4-pentanediol, 1,5-pentanediol, 1,6-hexanediol, and glycerol. 2-methyl-2,4-pentanediol is also known as hexanediol.
[0186] (10-3) Composition: Monoalkyl ethers of monoalkylene glycols having 2 to 4 carbon atoms and alkyl groups having 1 to 4 carbon atoms.
[0187] As a component of (10-3), for example, compounds selected from 1-methoxy-2-propanol and 1-ethoxy-2-propanol can be cited.
[0188] (10-4) Ingredients: Alkyl glycerol ethers having an alkyl group having 1 to 8 carbon atoms.
[0189] As a component of (10-4), examples include alkyl glycerides selected from 1-methylglycerol ether, 2-methylglycerol ether, 1,3-dimethylglycerol ether, 1-ethylglycerol ether, 1,3-diethylglycerol ether, triethylglycerol ether, 1-pentylglycerol ether, 2-pentylglycerol ether, 1-octylglycerol ether and 2-ethylhexylglycerol ether.
[0190] (10-5) Components: Aromatic alkyl ethers of monoalkylene glycols having 2 or 3 carbon atoms.
[0191] Examples of (10-5) components include 2-phenoxyethanol and 2-benzyloxyethanol.
[0192] From the viewpoint of further improving the storage stability at low temperatures, component (10) is preferably one or more compounds selected from components (10-1), (10-2), (10-3) and (10-4).
[0193] More specifically, the liquid laundry detergent composition of the present invention preferably contains ethanol and / or 2-phenoxyethanol.
[0194] The liquid laundry detergent composition of the present invention preferably contains ethanol and / or 2-phenoxyethanol as an organic solvent having hydroxyl groups.
[0195] The content of component (10) relative to 100% by mass of the composition is preferably 1 to 40% by mass, more preferably 4 to 20% by mass, and even more preferably 5 to 10% by mass.
[0196] (11) Water-soluble growth promoters
[0197] To improve the stability of the liquid laundry detergent composition, a water-soluble growth promoter can be incorporated. The water-soluble growth promoter of the present invention is an organic compound having an anionic group, and examples include alkylbenzene sulfonic acids or their salts containing one or two alkyl groups selected from methyl, ethyl, or propyl and having one sulfonic acid group or a carboxylic acid group, as well as benzoic acid or its salts. More specifically, it is p-toluenesulfonic acid, isopropylbenzenesulfonic acid, m-xylenesulfonic acid, or benzoic acid, with the salt preferably being an alkali metal salt. In the present invention, p-toluenesulfonic acid or its alkali metal salt is preferred, and it can also be incorporated in acid form and neutralized by an alkali agent in the composition. The liquid laundry detergent composition of the present invention may contain, preferably, 0.1 to 5% by mass (converted to an acidic compound), more preferably 0.5 to 4% by mass, and even more preferably 1 to 3% by mass of the water-soluble growth promoter.
[0198] The liquid laundry detergent composition of the present invention can exert excellent cleaning performance even at high surfactant concentrations, and is therefore suitable for use in concentrated liquid laundry detergents, etc.
[0199] The liquid laundry detergent composition of the present invention can also be used as a concentrated liquid laundry detergent in the form of a detergent packaging film as described later. In this case, the liquid laundry detergent composition may contain, for example, a component derived from the film. The liquid laundry detergent composition of the present invention can exhibit excellent cleaning performance even when containing a component derived from the film. Examples of components derived from the film include, for example, water-soluble polymers as described later.
[0200] The proportion of membrane-derived components in the above-mentioned liquid laundry detergent composition is not particularly limited, but is preferably 0 to 20% by mass relative to 100% by mass of the composition. More preferably, it is 0 to 15% by mass, and even more preferably, it is 0 to 10% by mass.
[0201] Furthermore, the proportion of the film-derived component in the above-mentioned liquid laundry detergent composition relative to 100% by mass of the surfactant is preferably 0.1 to 30% by mass. More preferably, it is 1 to 20% by mass, even more preferably 2 to 15% by mass, and particularly preferably 3 to 10% by mass.
[0202] [Composite Composition]
[0203] The present invention also relates to a composite composition which is a composite composition in which a liquid laundry detergent composition is encapsulated in a film for detergent packaging. The liquid laundry detergent composition comprises a vinyl alcohol polymer and a surfactant. The vinyl alcohol polymer has a structural unit (a) shown in formula (1) above, and optionally has a structural unit (b) shown in formula (2) above, and other structural units (c) other than the above structural units (a) and (b). The content ratio of each structural unit is 50-100 / 0-50 / 0-20 mol% relative to the total amount of all structural units (100 mol%). Thus, the proportion of cleaning components in the liquid laundry detergent composition can be further increased.
[0204] The preferred embodiment of the liquid laundry detergent composition in the above-described composite composition is as described in the section on liquid laundry detergent composition.
[0205] The detergent packaging film in the above composite composition is not particularly limited as long as it can seal the liquid laundry detergent composition of the present invention, and is preferably water-soluble. More preferably, it is a water-soluble polymer.
[0206] Examples of water-soluble polymers include polyvinyl alcohol, polyalkylene glycol, starch or modified starch, cellulose or modified cellulose, polyacrylate, polymethacrylate, polyacrylamide, and polyvinylpyrrolidone. One or more of these can be used. Polyvinyl alcohol is preferred.
[0207] The average degree of polymerization of the polymer constituting the above-mentioned membrane is not particularly limited, but is preferably 500 to 10,000, more preferably 1,000 to 8,000, and even more preferably 1,000 to 5,000.
[0208] The thickness of the above-mentioned membrane is not particularly limited, but is preferably 20 μm to 150 μm. More preferably, it is 35 μm to 125 μm, and even more preferably, it is 50 μm to 100 μm.
[0209] Example
[0210] The following examples further illustrate the present invention in detail, but the present invention is not limited to these examples. It should be noted that, unless otherwise stated, "parts" refers to "parts by weight" and "%" refers to "% by mass".
[0211] <Determination of Average Degree of Polymerization>
[0212] The average degree of polymerization of the polymer can be determined using the method described in JIS K6726. Alternatively, the average degree of polymerization of the polymer can also be determined by GPC testing.
[0213] Apparatus: Waters Alliance HPLC
[0214] Detector: RI
[0215] Columns: Shodex OHpak SB-806M HQ x 3
[0216] Temperature: 40℃
[0217] Flow rate: 1.0 mL / min
[0218] Calibration curves: PEG standard samples prepared by GL Sciences, Mw=194, 410, 615, 1020, 1450, 3860, 8160, 16100, 21160, 49930, 67600, 96100, 205500, 542500, 942000
[0219] Eluent: 100mM sodium phosphate aqueous solution / acetonitrile = 92 / 8
[0220] <Determination of Saponification Degree>
[0221] The degree of saponification of the polymer can be determined using the method described in JIS K6726. Alternatively, the degree of saponification of the polymer can also be determined by... 1 The results were obtained from H NMR measurements. The following is from... 1 The degree of saponification of the polymer obtained in the manufacturing example was calculated by H NMR determination.
[0222] Apparatus: VNMRS600 manufactured by Varian
[0223] Nuclide: 1 H
[0224] Resonant frequency: 600MHz
[0225] Signal acquisition time: 3.4 seconds
[0226] Delay time: 5 seconds
[0227] Solvent: Dimethyl sulfoxide-d6
[0228] Total number of times: 16
[0229] The calculation is based on the ratio of the peak area of 1.90–2.30 ppm (derived from the acetate in the side chain) to the peak area of 1.20–1.90 ppm (derived from the methylene protons in the polymer backbone).
[0230] <Evaluation of the cleaning power of dirt and grime 1>
[0231] [Cleaning Process]
[0232] (1) For mud-contaminated cloth KC-140 (manufactured by Warwick Equest) and standard white cloth, the DigiEye system (manufactured by VeriVide) was used to measure... , , The value of .
[0233] (2) Add 956.3g of ion-exchanged water to 59.0g of calcium chloride dihydrate and 27.2g of magnesium chloride hexahydrate to prepare hard water mother liquor (i).
[0234] (3) Mix 15.5g of sodium bicarbonate, 884.5g of pure water and 100g of 0.1M HCl aqueous solution to prepare 1000g of alkaline solution (ii).
[0235] (4) Prepare a 1% polymer aqueous solution by ion-exchanging water with a polymer solid content of 1%.
[0236] (5) Add 197.03 g of ion-exchanged water to 47.37 g of sodium alkylbenzene sulfonate (hereinafter referred to as LAS) aqueous solution (Neopelex G25, manufactured by Kao Corporation) and stir to prepare a 5% LAS aqueous solution (iii).
[0237] (6) Add 4090.4g of ion-exchanged water to 21.0g of hard water mother liquor (i) and stir. Add 0.2g of commercially available detergent packaging film, 84.0g of 5% LAS aqueous solution (iii), and 4.4g of alkaline solution (ii) and stir to prepare detergent solution (iv).
[0238] (7) Using a Tergot-o-meter (manufactured by Daeyoshi Corporation, product name: TM-4), add 995.0g of detergent solution (iv) to each of the four containers and adjust the temperature to 35°C.
[0239] (8) Add 5.0g of ion-exchanged water or 1% polymer aqueous solution to the container and stir for 1min.
[0240] (9) After adding 3 mud-contaminated cloths and bath ratio adjustment cloths (total amount of cloth is 50g) to each tank, perform a 20min cleaning process at 120rpm.
[0241] (10) Take out the soiled cloth and the bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1 minute using a dehydrator.
[0242] [Rinsing Process]
[0243] (1) Add 4179.0g of ion-exchanged water to 21.0g of hard water mother liquor (i) and stir to prepare rinsing solution.
[0244] (2) Add 1000g of rinsing solution to the tank and adjust the temperature to 35℃. Then add the cleaned soiled cloth and the bath ratio adjustment cloth, stir at 120rpm for 3min, and rinse.
[0245] (3) Take out the soiled cloth and the bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1 minute using a dehydrator.
[0246] (4) Repeat the steps (1) to (3) again.
[0247] [Drying Process]
[0248] The soiled cloth, which had undergone washing and rinsing, was left to air dry overnight.
[0249] [Calculation of cleaning rate]
[0250] For the washed mud-contaminated cloth and standard white cloth, the DigiEye system was used to measure... , , The value of is calculated using the following formula (II). The Stain Removal Index (SRI) is the cleaning rate.
[0251] [Mathematical Expression 1]
[0252] <Evaluation of the cleaning power of dirt and grime 2>
[0253] Change step (5) in the [cleaning process] of the above <Evaluation of the cleaning power of mud and dirt 1> to the following step (5'), and perform the other steps in the same way, and calculate the cleaning rate SRI.
[0254] (5') Add 168.43 g of deionized water to 29.07 g of sodium alkylbenzene sulfonate (hereinafter referred to as LAS) aqueous solution (Neopelex G25, manufactured by Kao Corporation) and stir. Then add 2.50 g of polyoxyalkylene lauryl ether (hereinafter referred to as PAE) (EMULGEN108, manufactured by Kao Corporation) and stir to prepare a 5% LAS / PAE aqueous solution (iii').
[0255] <Biodegradation Test>
[0256] The obtained vinyl alcohol polymer was subjected to a biodegradability test according to OECD 301F.
[0257] Preparation of culture medium: Culture medium stock solutions A through D are prepared using the following method.
[0258] Solution A: Weigh 0.850g of potassium dihydrogen phosphate (KH2PO4), 2.175g of dipotassium hydrogen phosphate (K2HPO4), 6.7217g of disodium hydrogen phosphate dodecahydrate (Na2HPO4·12H2O), and 0.050g of ammonium chloride (NH4Cl) into a 50ml sample bottle, dissolve them in an appropriate amount of water, transfer the solution to a 100ml volumetric flask, and add water to the mark.
[0259] Solution B: Dissolve 3.640g of calcium chloride dihydrate (CaCl2·2H2O) in an appropriate amount of water, transfer to a 100ml volumetric flask, and add water to the mark.
[0260] Solution C: Dissolve 2.250g of magnesium sulfate heptahydrate (MgSO4·7H2O) in an appropriate amount of water, transfer to a 100ml volumetric flask, and add water to the mark.
[0261] Solution D: Dissolve 0.025g of ferric chloride hexahydrate (III) (FeCl3·6H2O) in an appropriate amount of water, transfer to a 100ml volumetric flask, and add water to the mark.
[0262] Temperature the stock solutions A through D of the above culture media to 25°C. Using a full-volume pipette, add 10 ml of solution A to a 1 L volumetric flask and dilute with approximately 800 ml of water. Then, using a full-volume pipette, add 1 ml of solutions B, C, and D respectively, and dilute to the mark with water at 25°C. Prepare multiple aliquots of the above culture media according to the required experimental volume. Transfer the prepared culture media to a 5 L beaker and mix, then bubble while stirring for at least 1 hour.
[0263] Preparation of sludge solution: The sludge used in the biodegradability test was obtained from the Minami-Suita Wastewater Treatment Plant. First, the concentration of the sludge obtained using the following method was determined. While stirring the sludge, bubbling was performed, and 5 ml was taken using a full-volume pipette and filtered through filter paper. Five sheets of filter paper containing the sludge were prepared, dried in a desiccator at 105°C for 1 hour, and the sludge concentration was calculated based on the average weight loss of the five sheets. The sludge was then diluted with the culture medium prepared above to prepare a 1000 ppm sludge solution.
[0264] Preparation of polymer aqueous solutions: The obtained polymer was diluted with pure water to obtain a 2% (w / w) aqueous solution of the polymer. Additionally, sodium benzoate was diluted with pure water as a standard to obtain a 2% (w / w) aqueous solution of sodium benzoate.
[0265] BOD test: BOD was determined using a pressure sensor-type BOD analyzer. 144.75 g of the prepared culture medium was measured into the incubation flask, and 0.75 g of a 2% polymer aqueous solution was added. For the blank assay, 0.75 g of pure water was added, and for the standard assay, 0.75 g of a 2% sodium benzoate aqueous solution was added. The pH of the solution was then measured and adjusted using 0.1 M hydrochloric acid to achieve a pH of 7.4 ± 0.2. Then, 4.5 ml of 1000 ppm sludge solution was added as the test solution. After placing a stir bar in the incubation flask, 1.8 g of CO2 absorbent (Yabashi lime) was loaded into the CO2 absorbent holder, and the holder was installed, along with the BOD sensor. The incubation flask with the BOD sensor was stirred in a 24°C constant temperature bath, and the BOD value was calculated using the pressure sensor.
[0266] Degradation rate calculation: Calculate the theoretical oxygen demand (ppm) of the polymer, and calculate the degradation rate based on the difference between the BOD value determined in the blank test and the BOD value determined using the polyoxyalkylene compound. The degradation rate 28 days after the start of the experiment is taken as the biodegradation rate.
[0267] [Mathematical expression]
[0268] Degradation rate (%) = (Biochemical oxygen demand derived from the polymer) / (Theoretical oxygen demand of the polymer) × 100
[0269] <Manufacturing Example 1>
[0270] 53.36 g of ethanol (manufactured by Fujifilm and Kojin Chemical Co., Ltd.) was added to a glass reaction vessel equipped with a thermometer, nitrogen inlet tube, reflux condenser, and stirrer. After purging the reaction vessel with nitrogen, the temperature was raised to 60°C while stirring. Under stirring, 75.00 g of vinyl acetate (manufactured by Fujifilm and Kojin Chemical Co., Ltd.) and a mixed solution of initiator (2.16 g of 2,2'-azobis(2,4-dimethylpentanonitrile) (manufactured by Fujifilm and Kojin Chemical Co., Ltd., V-65) and 19.47 g of ethanol) were added dropwise to the 60°C reaction vessel through different drop nozzles. The vinyl acetate and initiator solution were added simultaneously, with the vinyl acetate addition taking 180 minutes and the initiator solution addition taking 240 minutes. After all additions were completed, the reaction solution was further heated at 60°C for 8 hours to obtain a polyvinyl acetate solution.
[0271] Next, 120.00 g of the obtained polyvinyl acetate solution was added to a glass reaction vessel equipped with a thermometer and a stirrer, along with 180 g of methanol. The mixture was heated to 50°C while stirring to form a homogeneous solution. Then, 13.94 g of a 4% sodium hydroxide-methanol suspension was added, and the mixture was stirred while maintaining the temperature at 50°C. After 120 minutes, the precipitation of polymer was confirmed. The reactants were filtered using a Kiriyama funnel, and the precipitate was recovered. The precipitate was then dried under reduced pressure at 60°C for 3 hours to obtain polymer 1. The degree of polymerization was 192, and the degree of saponification was 97%.
[0272] <Manufacturing Example 2>
[0273] 17.30 g of ethanol was added to a glass reaction vessel equipped with a thermometer, nitrogen inlet tube, reflux condenser, and stirrer. After purging the reaction vessel with nitrogen, the temperature was raised to 60°C while stirring. Under stirring, 75.00 g of vinyl acetate and an initiator solution (a mixture of 8.66 g of V-65 and 49.05 g of ethanol) were added dropwise to the 60°C reaction vessel through different drop nozzles. The vinyl acetate and initiator solution were added simultaneously, with the vinyl acetate addition taking 180 minutes and the initiator solution addition taking 240 minutes. After all additions were completed, the reaction solution was further heated at 60°C for 8 hours to mature, yielding a polyvinyl acetate solution.
[0274] Next, 12.47 g of the obtained polyvinyl acetate solution and 17.53 g of methanol were added to a glass reaction vessel equipped with a thermometer and a stirrer chip. The mixture was heated to 40°C while stirring to form a homogeneous solution. Then, 1.39 g of a 2% sodium hydroxide-methanol solution was added, and the mixture was stirred while maintaining the temperature at 40°C. After 17 minutes, the precipitation of polymer was confirmed. 0.69 g of 1M hydrochloric acid was added and the reaction was stopped by thorough stirring. The reactants were collected in a round-bottom flask, and the solvent was removed by distillation using an evaporator. The mixture was then dried under reduced pressure at 60°C for 3 hours to obtain polymer 2. The degree of polymerization was 157, and the degree of saponification was 88%.
[0275] <Manufacturing Example 3>
[0276] 53.78 g of ethanol was added to a glass reaction vessel equipped with a thermometer, nitrogen inlet tube, reflux condenser, and stirrer. After purging the reaction vessel with nitrogen, the temperature was raised to 60°C while stirring. Under stirring, two solutions were added dropwise to the 60°C reaction vessel: a monomer solution (a mixture of 150.00 g vinyl acetate, 3.70 g 3-mercaptopropionic acid, and 38.43 g ethanol) and an initiator solution (a mixture of 4.33 g V-65 and 49.77 g ethanol). The monomer and initiator solutions were added simultaneously, with the monomer solution added over 180 minutes and the initiator solution over 240 minutes. After all additions were completed, the reaction solution was further heated at 60°C for 8 hours to obtain a polyvinyl acetate solution.
[0277] Next, 12.47 g of the obtained polyvinyl acetate solution and 17.72 g of methanol were added to a glass reaction vessel equipped with a thermometer and a stir bar. The mixture was heated to 40°C while stirring to form a homogeneous solution. Then, 4.18 g of a 2% sodium hydroxide-methanol solution was added, and the mixture was stirred while maintaining the temperature at 40°C. After 120 minutes, the precipitation of polymer was confirmed. 2.09 g of 1M hydrochloric acid was added and the reaction was stopped by thorough stirring. The reactants were collected in a round-bottom flask, and the solvent was removed by distillation using an evaporator. The mixture was then dried under reduced pressure at 60°C for 3 hours to obtain polymer 3. The degree of polymerization was 110, and the degree of saponification was 72%.
[0278] <Manufacturing Example 4>
[0279] 153.41 g of the polyvinyl acetate solution from Preparation Example 3 was added to a glass reaction vessel equipped with a thermometer and a stirrer, along with 221.59 g of methanol. The mixture was heated to 40°C while stirring to form a homogeneous solution. Next, 34.85 g of a 2% sodium hydroxide-methanol solution was added, and the mixture was stirred while maintaining the temperature at 40°C. After 120 minutes, polymer precipitation was confirmed. The reactants were filtered using a Kiriyama funnel, and the precipitate was recovered. The precipitate was then dried under reduced pressure at 60°C for 3 hours to obtain polymer 4. The degree of polymerization was 110, and the degree of saponification was 93%.
[0280] <Manufacturing Example 5>
[0281] 12.30 g of the polyvinyl acetate solution from Preparation Example 3 was added to a glass reaction vessel equipped with a thermometer and a stir bar. 17.74 g of methanol was also added, and the mixture was heated to 40°C while stirring to form a homogeneous solution. Next, 4.19 g of a 2% sodium hydroxide-methanol solution was added, and the mixture was stirred while maintaining the temperature at 40°C. After 70 minutes, 2.09 g of 1M hydrochloric acid was added and the reaction was stopped by thorough stirring. The reactants were collected in a round-bottom flask, and the solvent was removed by distillation using an evaporator. The mixture was then dried under reduced pressure at 60°C for 3 hours to obtain polymer 5. The degree of polymerization was 110, and the degree of saponification was 57%.
[0282] <Manufacturing Example 6>
[0283] 58.41 g of ethanol was added to a glass reaction vessel equipped with a thermometer, nitrogen inlet tube, reflux condenser, and stirrer. After purging the reaction vessel with nitrogen, the temperature was raised to 60°C while stirring. Under stirring, two solutions were added dropwise to the 60°C reaction vessel: a monomer solution (a mixture of 150.00 g of vinyl acetate and 37.50 g of ethanol) and an initiator solution (a mixture of 4.33 g of V-65 and 49.77 g of ethanol). The monomer and initiator solutions were added simultaneously, with the monomer solution added over 180 minutes and the initiator solution over 240 minutes. After all additions were completed, the reaction solution was further heated at 60°C for 11 hours to obtain a polyvinyl acetate solution.
[0284] Next, 12.12 g of the obtained polyvinyl acetate solution and 17.72 g of methanol were added to a glass reaction vessel equipped with a thermometer and a stir bar. The mixture was heated to 40°C while stirring to form a homogeneous solution. Then, 1.41 g of a 2% sodium hydroxide-methanol solution was added, and the mixture was stirred while maintaining the temperature at 40°C. After 40 minutes, the precipitation of polymer was confirmed. 0.70 g of 1M hydrochloric acid was added and the reaction was stopped by thorough stirring. The reactants were collected in a round-bottom flask, and the solvent was removed by distillation using an evaporator. The mixture was then dried under reduced pressure at 60°C for 3 hours to obtain polymer 6. The degree of polymerization was 185, and the degree of saponification was 77%.
[0285] <Manufacturing Example 7>
[0286] 12.20 g of the polyvinyl acetate solution from Preparation Example 6 was added to a glass reaction vessel equipped with a thermometer and a stir bar, along with 17.70 g of methanol. The mixture was heated to 40°C while stirring to form a homogeneous solution. Next, 1.41 g of a 2% sodium hydroxide-methanol solution was added, and the mixture was stirred while maintaining the temperature at 40°C. After 28 minutes, 0.70 g of 1M hydrochloric acid was added and the reaction was stopped by thorough stirring. The reactants were collected in a round-bottom flask, and the solvent was removed by distillation using an evaporator. The mixture was then dried under reduced pressure at 60°C for 3 hours to obtain polymer 7. The degree of polymerization was 185, and the degree of saponification was 59%.
[0287] <Manufacturing Example 8>
[0288] 56.10 g of ethanol was added to a glass reaction vessel equipped with a thermometer, nitrogen inlet tube, reflux condenser, and stirrer. After purging the reaction vessel with nitrogen, the temperature was raised to 60°C while stirring. Under stirring, two solutions were added dropwise to the 60°C reaction vessel: a monomer solution (a mixture of 150.00 g vinyl acetate, 1.85 g 3-mercaptopropionic acid, and 37.96 g ethanol) and an initiator solution (a mixture of 4.33 g V-65 and 49.77 g ethanol). The monomer and initiator solutions were added simultaneously, with the monomer solution added over 180 minutes and the initiator solution over 240 minutes. After all additions were completed, the reaction solution was further heated at 60°C for 11 hours to obtain a polyvinyl acetate solution.
[0289] Next, 153.27 g of the obtained polyvinyl acetate solution and 221.73 g of methanol were added to a glass reaction vessel equipped with a thermometer and a stirrer. The mixture was heated to 40°C while stirring to form a homogeneous solution. Then, 34.80 g of a 2% sodium hydroxide-methanol solution was added, and the mixture was stirred while maintaining the temperature at 40°C. After 450 minutes, the precipitation of polymer was confirmed. The reactants were filtered using a Kiriyama funnel, and the precipitate was recovered. The precipitate was then dried under reduced pressure at 60°C for 3 hours to obtain polymer 8. The degree of polymerization was 122, and the degree of saponification was 92%.
[0290] <Manufacturing Example 9>
[0291] 3.00 g of polyvinyl alcohol (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., polyvinyl alcohol 500, fully saponified type), with an average degree of polymerization of 500 and a saponification degree of approximately 98%, was added to a glass reaction vessel equipped with a thermometer and a stir bar. 40.00 g of pure water was added, and the mixture was heated to 90°C while stirring to prepare a homogeneous solution. After cooling the solution to 50°C, 4.99 g of a 1% sodium periodate aqueous solution was added, and the mixture was stirred while maintaining the temperature at 50°C. After 240 minutes, the reactants were recovered to obtain polymer 9, with a degree of polymerization of 365 and a saponification degree of 98%.
[0292] <Manufacturing Example 10>
[0293] 105.04 g of polyvinyl alcohol (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., polyvinyl alcohol 1000, partially saponified type), with an average degree of polymerization of 1000 and a saponification degree of approximately 87%, was added to a glass reaction vessel equipped with a thermometer and a stirrer. 586.60 g of pure water was added, and the mixture was heated to 90°C while stirring to prepare a homogeneous solution. After cooling the solution to 50°C, 8.40 g of a 10% sodium periodate aqueous solution was added, and the mixture was stirred while maintaining the temperature at 50°C. After 240 minutes, the reactants were recovered to obtain polymer 10, with a degree of polymerization of 458 and a saponification degree of 87%.
[0294] <Polymer 11>
[0295] Polyvinyl alcohol (manufactured by SIGMA-ALDRICH, Mw9000-10000, saponification degree 80%) with an average degree of polymerization of 262 and a degree of saponification of 80% was used.
[0296] <Polymer 12>
[0297] Polyvinyl alcohol (manufactured by Fujifilm and Koh Genuine Pharmaceutical Co., Ltd., polyvinyl alcohol 1000, fully saponified type) with an average degree of polymerization of 500 and a saponification degree of approximately 98% was used.
[0298] <Polymer 13>
[0299] Polyvinyl alcohol (manufactured by Fujifilm and Kojun Pharmaceutical Co., Ltd., polyvinyl alcohol 500, partially saponified type) with an average degree of polymerization of 500 and a degree of saponification of about 87% was used.
[0300] <Manufacturing Example 14>
[0301] 5.01 g of polyvinyl alcohol (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., polyvinyl alcohol 500, fully saponified type), with an average degree of polymerization of 500 and a saponification degree of approximately 98%, was added to a glass reaction vessel equipped with a thermometer and a stir bar. 40.00 g of pure water was added, and the mixture was heated to 90°C while stirring to prepare a homogeneous solution. After cooling the solution to 50°C, 5.00 g of a 2% sodium periodate aqueous solution was added, and the mixture was stirred while maintaining the temperature at 50°C. After 240 minutes, the reactants were recovered to obtain polymer 14, with a degree of polymerization of 262 and a saponification degree of 98%.
[0302] <Manufacturing Example 15>
[0303] 6.01 g of polyvinyl alcohol (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., polyvinyl alcohol 500, partially saponified type), with an average degree of polymerization of 500 and a saponification degree of approximately 87%, was added to a glass reaction vessel equipped with a thermometer and a stir bar. 32.79 g of pure water was added, and the mixture was heated to 90°C while stirring to form a homogeneous solution. After cooling the solution to 50°C, 1.20 g of a 10% sodium periodate aqueous solution was added, and the mixture was stirred while maintaining the temperature at 50°C. After 240 minutes, the reactants were recovered to obtain polymer 15, with a degree of polymerization of 279 and a saponification degree of 87%.
[0304] <Manufacturing Example 16>
[0305] 105.00 g of polyvinyl alcohol (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., polyvinyl alcohol 500, partially saponified type) with an average degree of polymerization of 500 and a saponification degree of approximately 87% was added to a glass reaction vessel equipped with a thermometer and a stirrer. 573.98 g of pure water was added, and the mixture was heated to 90°C while stirring to prepare a homogeneous solution. After cooling the solution to 50°C, 21.05 g of a 10% sodium periodate aqueous solution was added dropwise over 20 minutes using a dropping funnel, while maintaining the temperature at 50°C and stirring. After 240 minutes, the reactants were recovered to obtain polymer 16, with a degree of polymerization of 266 and a saponification degree of 87%.
[0306] <Manufacturing Example 17>
[0307] 105.01 g of polyvinyl alcohol (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., polyvinyl alcohol 500, partially saponified type) with an average degree of polymerization of 500 and a saponification degree of approximately 87% was added to a glass reaction vessel equipped with a thermometer and a stirrer. 532.01 g of pure water was added, and the mixture was heated to 90°C while stirring to prepare a homogeneous solution. After cooling the solution to 50°C, 63.02 g of a 10% sodium periodate aqueous solution was added dropwise over 20 minutes using a dropping funnel, while maintaining the temperature at 50°C and stirring. After 240 minutes, the reactants were recovered to obtain polymer 17, with a degree of polymerization of 122 and a saponification degree of 87%.
[0308] <Manufacturing Example 18>
[0309] 105.01 g of polyvinyl alcohol (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., polyvinyl alcohol 1000, partially saponified type), with an average degree of polymerization of 1000 and a saponification degree of approximately 87%, was added to a glass reaction vessel equipped with a thermometer and a stirrer. 586.60 g of pure water was added, and the mixture was heated to 90°C while stirring to prepare a homogeneous solution. After cooling the solution to 50°C, 8.39 g of a 5% sodium periodate aqueous solution was added, and the mixture was stirred while maintaining the temperature at 50°C. After 120 minutes, the reactants were recovered to obtain polymer 18, with a degree of polymerization of 610 and a saponification degree of 87%.
[0310] <Comparative Polymer 1>
[0311] Polyvinyl alcohol (manufactured by Fujifilm and Koujun Pharmaceutical Co., Ltd., polyvinyl alcohol 3500, partially saponified type) with an average degree of polymerization of 3500 and a saponification degree of about 88% was used.
[0312] <Comparative Polymers 2>
[0313] Polyvinyl alcohol (manufactured by Fujifilm and Koujun Pharmaceutical Co., Ltd., with an average degree of polymerization of 1650 and a saponification degree of about 80%) was used.
[0314] <Comparative Polymers 3>
[0315] Polyvinyl alcohol (manufactured by Fujifilm and Koh Genuine Pharmaceutical Co., Ltd., polyvinyl alcohol 1000, fully saponified type) with an average degree of polymerization of 1000 and a saponification degree of about 96% was used.
[0316] <Comparative Polymers 4>
[0317] Polyvinyl alcohol (manufactured by Fujifilm and Koh Genuine Pharmaceutical Co., Ltd., with an average degree of polymerization of 1500 and a saponification degree of approximately 88%) was used.
[0318] The degree of polymerization and degree of saponification of polymers 1 to 18 are shown in Table 1, and the degree of polymerization and degree of saponification of polymers 1 to 4 are shown in Table 2.
[0319] [Table 1]
[0320] [Table 2]
[0321] <Examples 1-3 and Comparative Examples 1-3>
[0322] The cleaning power evaluation 1 described above was performed using polymers 1-3 obtained in Manufacturing Examples 1-3 and comparative polymers 1-3 obtained in Comparative Manufacturing Examples 1-3, along with surfactants. The results are shown in Table 3.
[0323] [Table 3]
[0324] <Examples 4 and 5 and Comparative Example 4>
[0325] The cleaning power evaluation 2 described above was performed using polymers 1 and 4 obtained in Manufacturing Examples 1 and 4, and comparative polymer 3 obtained in Comparative Manufacturing Example 3, along with surfactants. The results are shown in Table 4.
[0326] [Table 4]
[0327] <Compatibility Tests for Liquid Laundry Detergent Complexes>
[0328] [Preparation of liquid laundry detergent complexes]
[0329] Liquid laundry detergent complexes were prepared using the following method.
[0330] Dissolve 0.50 g of lauric acid in 1.00 g of 99.5% ethanol. Add 29.52 g of deionized water to 9.23 g of sodium alkylbenzene sulfonate (hereinafter referred to as LAS) aqueous solution (Neopelex G65, manufactured by Kao Corporation), stir thoroughly, then add 4.00 g of propylene glycol and 4.00 g of polyoxyethylene lauryl ether (hereinafter referred to as PAE) (EMULGEN 108, manufactured by Kao Corporation), followed by 0.75 g of anhydrous citric acid, and stir thoroughly. Add the pre-dissolved lauric acid and ethanol mixture and stir. Then add 1.00 g of 2-aminoethanol and stir thoroughly to prepare a liquid laundry detergent complex with a surfactant concentration of 20%.
[0331] Dissolve 0.50 g of lauric acid in 1.00 g of 99.5% ethanol. Add 36.13 g of deionized water to 4.62 g of sodium alkylbenzene sulfonate (hereinafter referred to as LAS) aqueous solution (Neopelex G65, manufactured by Kao Corporation), stir thoroughly, then add 4.00 g of propylene glycol and 2.00 g of polyoxyethylene lauryl ether (hereinafter referred to as PAE) (EMULGEN 108, manufactured by Kao Corporation), followed by 0.75 g of anhydrous citric acid, and stir thoroughly. Add the pre-dissolved lauric acid and ethanol mixture and stir. Then add 1.00 g of 2-aminoethanol and stir thoroughly to prepare a liquid laundry detergent complex with a surfactant concentration of 10%.
[0332] Dissolve 0.50 g of lauric acid in 1.00 g of 99.5% ethanol. Add 22.90 g of deionized water to 13.85 g of an aqueous solution of sodium alkylbenzene sulfonate (hereinafter referred to as LAS) (Neopelex G65, manufactured by Kao Corporation), stir thoroughly, then add 4.00 g of propylene glycol and 6.00 g of polyoxyethylene lauryl ether (hereinafter referred to as PAE) (EMULGEN 108, manufactured by Kao Corporation), followed by 0.75 g of anhydrous citric acid, and stir thoroughly. Add the pre-dissolved lauric acid and ethanol mixture and stir. Then add 1.00 g of 2-aminoethanol and stir thoroughly to prepare a liquid laundry detergent complex with a surfactant concentration of 30%.
[0333] [Compatibility Test]
[0334] For polymers 1, 5, 6, 7, 8, 11, 12, 13 and comparative polymers 3 and 4, aqueous solutions of polymers were prepared at a polymer concentration of 20%. Compatibility tests were conducted using these aqueous solutions and polymers 9 and 10. To 2.0 g of each prepared liquid laundry detergent complex at each surfactant concentration, polymer was added at a polymer concentration of 1%, and the solution was thoroughly stirred. The stirred solution was placed in a dish with a 10 mm optical path length, and the transmittance was measured using a UV meter (UV-1800, manufactured by Shimadzu Corporation). A solution with a transmittance of 50% or higher at 550 nm was considered compatible. Compatibility was recorded as 1, and incompatibility as 0. The results are shown in Table 5.
[0335] [Table 5]
[0336] [Calculation of the regression equation representing the range of compatibility]
[0337] The surfactant concentration, average degree of polymerization (DP), and degree of saponification of the vinyl alcohol polymer (VAP) in the evaluation solution used to assess the compatibility of the liquid laundry detergent complex (liquid laundry detergent composition) were used to calculate the regression equation for determining the compatibility range between the VAP and the liquid laundry detergent. The results shown in Table 5 were input into the statistical software JMP (developed by SAS). In the JMP model fitting, the compatibility results were substituted as the nominal scale into the target variable, and the surfactant concentration (%) in the compatibility evaluation solution, the average degree of polymerization (DP) of the VAP, and the degree of saponification (mol%) of the VAP were used as explanatory variables for logistic regression. The predictive equation for the compatibility probability was calculated through logistic regression. With three significant figures in the predictive equation, the resulting equation is shown below. When the compatibility probability is ≥0.5, the VAP is well soluble in the liquid laundry detergent complex.
[0338] [Mathematical Expression 2]
[0339] [Compatibility test by adding PEG compound]
[0340] As PEG compounds, an 80% aqueous solution of polyethyleneimine ethoxylate (PN-100, manufactured by Nippon Shokubai Co., Ltd.) was prepared as PEG compound 1, and an 80% aqueous solution of polyethylene glycol 6000 (manufactured by Fujifilm and Koh Genuine Chemicals Co., Ltd.) was prepared as PEG compound 2.
[0341] For polymer 13, an aqueous solution was prepared at a polymer concentration of 20%. Compatibility tests were conducted using this aqueous solution and polymers 13-15. To 2.0 g of the liquid laundry detergent complexes at the above surfactant concentrations, polymers were added at a polymer concentration of 1%, and the solution was thoroughly stirred. The transmittance of the stirred solution was measured, and compatibility with the liquid laundry detergent complexes was determined in the same manner as above. Then, the above PEG compounds were added at the concentrations shown in Table 6, and after stirring, compatibility was determined again. The results are shown in Table 6. The addition of PEG compounds improved the compatibility between the vinyl alcohol polymers and the liquid laundry detergent complexes. Furthermore, when an equal amount of ion-exchanged water as the PEG compounds shown in Table 6 was added to a mixture of the liquid laundry detergent complexes and polymers with a compatibility determination of 0, no improvement in compatibility was observed.
[0342] [Table 6]
[0343] <Evaluation of Enzyme Activity>
[0344] The activity of enzymes (proteases) is evaluated using the following methods.
[0345] [Preparation of casein solution]
[0346] Weigh 0.65g of casein (manufactured by Fujifilm and Koko Pure Chemical Industries Co., Ltd.) and 37.5g of 0.1N sodium hydroxide (manufactured by Fujifilm and Koko Pure Chemical Industries Co., Ltd.) into a beaker and stir until dissolved. Add 0.62g of sodium dihydrogen phosphate dihydrate (manufactured by Fujifilm and Koko Pure Chemical Industries Co., Ltd.), then add 61.85g of deionized water and stir to prepare a casein solution.
[0347] Preparation of trichloroacetic acid (TCA) solution
[0348] A TCA solution was prepared by weighing 7.10 g of trichloroacetic acid (TCA) (manufactured by Fujifilm and Koichi Chemical Co., Ltd.) and 92.9 g of deionized water into a plastic bottle.
[0349] [Preparation of sample solution]
[0350] To prepare a hard water mother liquor, 956.3 g of deionized water was added to 59.0 g of calcium chloride dihydrate and 27.2 g of magnesium chloride hexahydrate. Then, 0.5 g of the mother liquor was diluted 1000 times to prepare 3 dH hard water. For polymers 1 and 16, the 3 dH hard water was used to dilute the polymers to a concentration of 1% for the vinyl alcohol polymers, and then the pH was adjusted to 7.5–8.5 with a 0.01 N sodium hydroxide aqueous solution.
[0351] 0.1g of PU100L (manufactured by Novozymes), which is used as a protease, was diluted 100 times to prepare a 1% enzyme aqueous solution.
[0352] Add 24.9g of 3dH hardness water to 0.1g of 1% enzyme aqueous solution to prepare a blank sample solution. Add 0.25g of the above-mentioned pH-adjusted 1% polymer aqueous solution to 0.1g of 1% enzyme aqueous solution, then add 24.65g of 3dH hardness water to prepare a sample solution.
[0353] [Enzyme Activity Evaluation]
[0354] Add 3 mL of casein solution to a screw-cap tube using a micropipette and incubate at 37°C. While stirring the casein solution in the incubator at 37°C, add 3 mL of sample solution using a micropipette and stir for 10 minutes. After stirring for 10 minutes, add 3 mL of TCA solution and maintain the temperature for 30 minutes to stop the enzyme reaction. Filter the reaction solution through a 0.45 μm syringe filter, and add 3 mL to a UV cell. Measure the absorbance at 280 nm using a UV meter. Record the measured absorbance as the "absorbance after enzyme reaction".
[0355] Add 3 mL of casein solution to a screw-cap tube using a micropipette. After adjusting the temperature in a 37°C incubator, add 3 mL of TCA solution and stir. Then, add 3 mL of sample solution. Filter the solution through a 0.45 μm syringe filter, add 3 mL to the UV cell, and measure the absorbance at 280 nm using a UV meter. The measured absorbance is recorded as the "unreacted absorbance". The difference between the "absorbance after enzyme reaction" and the "unreacted absorbance" is calculated as Δabsorbance. The results are shown in Table 7. A higher Δabsorbance indicates a greater amount of amino acids in the filtrate and higher enzyme activity.
[0356] [Table 7]
[0357] <Evaluation of Sebum Cleansing Power>
[0358] [Cleaning Process]
[0359] (1) For sebum-stained cloth WFK 20D and standard white cloth, the DigiEye system (manufactured by VeriVide) was used to measure... , , The value of .
[0360] (2) Add 956.3g of ion-exchanged water to 59.0g of calcium chloride dihydrate and 27.2g of magnesium chloride hexahydrate to prepare hard water mother liquor (i).
[0361] (3) Mix 15.5g of sodium bicarbonate, 884.5g of pure water and 100g of 0.1M HCl aqueous solution to prepare 1000g of alkaline solution (ii).
[0362] (4) Prepare a 1% polymer aqueous solution using ion-exchanged water so that the solid content of the polymer is 1%.
[0363] (5) Add 197.03 g of ion-exchanged water to 47.37 g of sodium alkylbenzene sulfonate (hereinafter referred to as LAS) aqueous solution (Neopelex G25, manufactured by Kao Corporation) and stir to prepare a 5% LAS aqueous solution (iii).
[0364] (6) Add 4091.7g of ion-exchanged water to 21.0g of hard water mother liquor (i) and stir. Add 84.0g of 5% LAS aqueous solution (iii) and 3.4g of alkaline solution (ii) and stir to prepare detergent solution (iv).
[0365] (7) Using a Tergot-o-meter (manufactured by Daeyoshi Corporation, product name: TM-4), add 995.0g of detergent solution (iv) to each of the four containers and adjust the temperature to 35°C.
[0366] (8) Add 5.0g of ion-exchanged water or 1% polymer aqueous solution to the container and stir for 1min.
[0367] (9) After adding 5 sheets of sebum-contaminated cloth and bath ratio adjustment cloth (total amount of cloth is 50g) to each tank, perform a 20min cleaning process at 120rpm.
[0368] (10) Remove the soiled cloth and bath ratio adjustment cloth from each tank, squeeze out the water by hand, and dehydrate them for 1 minute using a dehydrator.
[0369] [Rinsing Process]
[0370] (1) Add 4179.0g of ion-exchanged water to 21.0g of hard water mother liquor (i) and stir to prepare rinsing solution.
[0371] (2) Add 1000g of rinsing solution to the tank and adjust the temperature to 35℃. Then add the cleaned soiled cloth and the bath ratio adjustment cloth, stir at 120rpm for 3min, and rinse.
[0372] (3) Take out the soiled cloth and the bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1 minute using a dehydrator.
[0373] (4) Repeat the steps (1) to (3) again.
[0374] [Drying Process]
[0375] The soiled cloth, which had undergone washing and rinsing, was left to air dry overnight.
[0376] [Calculation of cleaning rate]
[0377] For the mud-contaminated cloth and standard white cloth after washing, the DigiEye system was used for measurement. , , The value of is calculated. The cleaning rate SRI is then calculated, and the difference between it and the blank SRI is taken as ΔSRI. The results are shown in Table 8.
[0378] [Table 8]
[0379] <Biodegradability Evaluation>
[0380] The above biodegradability tests were conducted on polymers 4, 6, 12, 13, and 16–18, and the results are shown in Table 9.
[0381] [Table 9]
[0382] <Evaluation of dirt removal power 3>
[0383] [Cleaning Process]
[0384] (1) For mud-contaminated cloth KC-140 (Warwick Equest) and standard white cloth, measurements were taken using the DigiEye system (VeriVide) with a D65 light source. , , The value of .
[0385] (2) Add 956.3g of ion-exchanged water to 59.0g of calcium chloride dihydrate and 27.2g of magnesium chloride hexahydrate to prepare hard water mother liquor (i).
[0386] (3) Mix 15.5g of sodium bicarbonate, 884.5g of pure water and 100g of 0.1M HCl aqueous solution to prepare 1000g of alkaline solution (ii).
[0387] (4) Prepare a 1% polymer aqueous solution using ion-exchanged water so that the solid content of the polymer is 1%.
[0388] (5) Add 197.03 g of ion-exchanged water to 47.37 g of sodium alkylbenzene sulfonate (hereinafter referred to as LAS) aqueous solution (Neopelex G25, manufactured by Kao Corporation) and stir to prepare a 5% LAS aqueous solution (iii).
[0389] (6) Add 4170.8g of ion-exchanged water to 9.8g of hard water mother liquor (i) and stir. Add 15.1g of 5% LAS aqueous solution (iii) and 4.2g of alkaline solution (ii) and stir to prepare a detergent solution (iv) with pH 8.5.
[0390] (7) Using a Tergot-o-meter (manufactured by Daeyoshi Corporation, product name: TM-4), add 996.0g of detergent solution (iv) to each of the four containers and adjust the temperature to 32°C.
[0391] (8) Add 4.0g of ion-exchanged water or 1% polymer aqueous solution to the container and stir for 1min.
[0392] (9) After adding 3 mud-contaminated cloths and bath ratio adjustment cloths (total amount of cloth is 50g) to each tank, perform a 12-minute cleaning process at 100rpm.
[0393] (10) Remove the soiled cloth and bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1.5 minutes using a dehydrator.
[0394] [Rinsing Process]
[0395] (1) Add 4190.2g of ion-exchanged water to 9.8g of hard water mother liquor (i) and stir to prepare rinsing solution.
[0396] (2) Add 1000g of rinsing solution to the tank and adjust the temperature to 25°C. Then add the cleaned soiled cloth and the bath ratio adjustment cloth, stir at 100rpm for 3min, and rinse.
[0397] (3) Take out the soiled cloth and the bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1.5 minutes using a dehydrator.
[0398] [Drying Process]
[0399] The soiled cloth, which had undergone washing and rinsing, was left to air dry overnight.
[0400] [Calculation of cleaning rate]
[0401] For the washed mud-contaminated cloth and standard white cloth, measurements were taken using the DigiEye system with a D65 light source. , , The value of is calculated from the above formula (II) to obtain the cleaning rate SRI.
[0402] [Calculation of Re-contamination Prevention Capability]
[0403] For the uncontaminated white portion of the washed mud-contaminated cloth and the standard white cloth, a spectrophotometer (manufactured by Nippon Denshoku Kogyo Co., Ltd., product name: SE6000) was used with a D65 light source and a viewing angle of 2° to measure the difference. , , The value of . The white portion of the soiled cloth after washing and the standard white cloth are calculated using equation (III) above. The recontamination of the white cloth portion was evaluated. The smaller the value, the less likely recontamination has occurred, and the higher the ability to prevent recontamination.
[0404] <Dirty Cleaning Power Rating 4>
[0405] Change step (6) in the [cleaning process] of the above <Evaluation of the cleaning power of mud 3> to the following step (6'), and perform the other steps in the same way, and calculate the cleaning rate SRI and the ability to prevent recontamination. .
[0406] (6') 60.0 g of deionized water was added to 10.0 g of a cationic surfactant aqueous solution of dimethyl laurylamine oxide (Amphitol 20N, manufactured by Kao Corporation) and stirred to obtain a 5% dimethyl laurylamine oxide aqueous solution. 4175.1 g of deionized water was added to 9.8 g of hard water mother liquor (i) and stirred. Then, 11.3 g of 5% LAS aqueous solution (iii) and 3.8 g of 5% dimethyl laurylamine oxide aqueous solution were added and stirred to prepare a detergent solution (iv) with a pH of 8.5.
[0407] The cleaning efficiency ratio (SRI) and the anti-recontamination capability obtained from <Sludge Cleaning Power Evaluation 3> and <Sludge Cleaning Power Evaluation 4> are used together. The results are shown in Table 10. These results indicate that a lower proportion of cationic surfactants in the detergent complex results in higher dirt removal efficiency and better resistance to re-fouling.
[0408] [Table 10]
[0409] <Evaluation of Cleaning Power for Food Stains 1>
[0410] [Cleaning Process]
[0411] (1) For the butter-stained cloth KC-132 (Warwick Equest) and the standard white cloth, the staining was measured using the DigiEye system (VeriVide) with a D65 light source. , , The value of .
[0412] (2) Add 956.3g of ion-exchanged water to 59.0g of calcium chloride dihydrate and 27.2g of magnesium chloride hexahydrate to prepare hard water mother liquor (i).
[0413] (3) Mix 15.5g of sodium bicarbonate, 884.5g of pure water and 100g of 0.1M HCl aqueous solution to prepare 1000g of alkaline solution (ii).
[0414] (4) Prepare a 1% polymer aqueous solution using ion-exchanged water so that the solid content of the polymer is 1%.
[0415] (5) Add 197.03 g of ion-exchanged water to 47.37 g of sodium alkylbenzene sulfonate (hereinafter referred to as LAS) aqueous solution (Neopelex G25, manufactured by Kao Corporation) and stir to prepare a 5% LAS aqueous solution (iii).
[0416] (6) Add 4141.7g of ion-exchanged water to 9.8g of hard water mother liquor (i) and stir. Add 42.0g of 5% LAS aqueous solution (iii) and 6.4g of alkaline solution (ii) and stir to prepare a detergent solution (iv) with pH 8.5.
[0417] (7) Using a Tergot-o-meter (manufactured by Daeyoshi Corporation, product name: TM-4), add 996.0g of detergent solution (iv) to each of the four containers and adjust the temperature to 32°C.
[0418] (8) Add 4.0g of ion-exchanged water or 1% polymer aqueous solution to the container and stir for 1min.
[0419] (9) After adding 3 pieces of grease-stained cloth and bath ratio adjustment cloth (total amount of cloth is 50g) to each tank, perform a 12min cleaning process at 100rpm.
[0420] (10) Remove the soiled cloth and bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1.5 minutes using a dehydrator.
[0421] [Rinsing Process]
[0422] (1) Add 4190.2g of ion-exchanged water to 9.8g of hard water mother liquor (i) and stir to prepare rinsing solution.
[0423] (2) Add 1000g of rinsing solution to the tank and adjust the temperature to 25°C. Then add the cleaned soiled cloth and the bath ratio adjustment cloth, stir at 100rpm for 3min, and rinse.
[0424] (3) Take out the soiled cloth and the bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1.5 minutes using a dehydrator.
[0425] [Drying Process]
[0426] The soiled cloth, which had undergone washing and rinsing, was left to air dry overnight.
[0427] [Calculation of cleaning rate]
[0428] For the stained cloth and standard white cloth after washing, the stains were measured using the DigiEye system with a D65 light source. , , The value of is calculated from the above formula (II) to obtain the cleaning rate SRI.
[0429] <Evaluation of Cleaning Power for Food Stains 2>
[0430] Change step (6) in the [cleaning process] of the above <Evaluation of Cleaning Power of Food Dirt 1> to the following step (6'), and perform the other steps in the same way, and calculate the cleaning rate SRI.
[0431] (6') 60.0 g of deionized water was added to 10.0 g of a cationic surfactant aqueous solution of dimethyl laurylamine oxide (Amphitol 20N, manufactured by Kao Corporation) and stirred to obtain a 5% dimethyl laurylamine oxide aqueous solution. 4148.2 g of deionized water was added to 9.8 g of hard water mother liquor (i) and stirred. Then, 31.5 g of 5% LAS aqueous solution (iii) and 10.5 g of 5% dimethyl laurylamine oxide aqueous solution were added and stirred to prepare a detergent solution (iv) with a pH of 8.5.
[0432] The SRI (Sweeping Intake) results obtained from the above-mentioned food stain cleaning power evaluation 1 (0% cationic surfactant in the surfactant) and food stain cleaning power evaluation 2 (25% cationic surfactant in the surfactant) are shown in Table 11. These results indicate that a lower proportion of cationic surfactant in the detergent complex results in a higher food stain cleaning efficiency.
[0433] [Table 11]
[0434] <Dirty cleaning power rating 5>
[0435] [Preparation of liquid detergent complex 1 for evaluation]
[0436] The evaluation liquid detergent complex 1 was prepared by the following method.
[0437] 44.77 g of LAS aqueous solution (NEOPELEX G65, manufactured by Kao Corporation) was mixed with 55.23 g of deionized water to obtain a 29% LAS aqueous solution. 1.67 g of lauric acid was dissolved in a mixed solution of 0.84 g of 99.5% ethanol and 1.67 g of propylene glycol. 0.83 g of 2-aminoethanol, 1.67 g of sodium p-toluenesulfonate, and 4.17 g of deionized water were added to this solution, and the mixture was stirred thoroughly. 65.22 g of a 23% LAS aqueous solution and 2.50 g of citric acid were added to this solution, and the mixture was stirred. Then, 2.78 g of a 48% sodium hydroxide aqueous solution was added, and finally, 18.66 g of deionized water was added, and the mixture was stirred thoroughly. This yielded liquid detergent complex 1, an evaluation compound for detergents where the surfactant is solely LAS.
[0438] [Preparation of liquid detergent complex 2 for evaluation]
[0439] The evaluation liquid detergent complex 2 was prepared by the following method.
[0440] A 23% LAS aqueous solution was obtained by adding 64.62 g of deionized water to 35.38 g of LAS aqueous solution (NEOPELEX G65, manufactured by Kao Corporation) and stirring thoroughly. 1.67 g of lauric acid was dissolved in a mixed solution of 0.84 g of ethanol (99.5%) and 1.67 g of propylene glycol. Then, 0.83 g of 2-aminoethanol, 1.67 g of sodium p-toluenesulfonate, and 4.17 g of deionized water were added to this solution, followed by 2.50 g of PAE (EMULGEN 108, manufactured by Kao Corporation), and the mixture was stirred thoroughly. Next, 42.93 g of 29% LAS aqueous solution and 2.50 g of citric acid were added to this solution, followed by 2.78 g of 48% sodium hydroxide aqueous solution, and finally 38.45 g of deionized water, and the mixture was stirred thoroughly. This yielded liquid detergent complex 2, with LAS and PAE as surfactants in the detergent complex.
[0441] [Cleaning Process]
[0442] (1) For mud-contaminated cloth KC-140 (Warwick Equest) and standard white cloth, measurements were taken using the DigiEye system (VeriVide) with a D65 light source. , , The value of .
[0443] (2) Add 956.3g of ion-exchanged water to 59.0g of calcium chloride dihydrate and 27.2g of magnesium chloride hexahydrate to prepare hard water mother liquor (i).
[0444] (3) Prepare a 1% polymer aqueous solution using ion-exchanged water so that the solid content of the polymer is 1%.
[0445] (4) Add 4174.8g of ion-exchanged water to 21.0g of hard water mother liquor (i) and stir. Add 5.0g of evaluation liquid detergent complex 1 or evaluation liquid detergent complex 2 and stir to prepare detergent solution (ii).
[0446] (5) Using a Tergot-o-meter (manufactured by Daeyoshi Corporation, product name: TM-4), add 998.0g of detergent solution (ii) to each of the four containers and adjust the temperature to 32°C.
[0447] (6) Add 2.0g of ion-exchanged water or 1% polymer aqueous solution to the container and stir for 1min.
[0448] (7) After adding 3 mud-contaminated cloths and bath ratio adjustment cloths (total amount of cloth is 50g) to each tank, perform a 12-minute cleaning process at 100rpm.
[0449] (8) Remove the soiled cloth and bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1.5 minutes using a dehydrator.
[0450] [Rinsing Process]
[0451] (1) Add 4179.0g of ion-exchanged water to 21.0g of hard water mother liquor (i) and stir to prepare rinsing solution.
[0452] (2) Add 1000g of rinsing solution to the tank and adjust the temperature to 25°C. Then add the cleaned soiled cloth and the bath ratio adjustment cloth, stir at 100rpm for 3min, and rinse.
[0453] (3) Take out the soiled cloth and the bath ratio adjustment cloth from each tank, squeeze out the water by hand, and then dehydrate them for 1.5 minutes using a dehydrator.
[0454] [Drying Process]
[0455] The soiled cloth, which had undergone washing and rinsing, was left to air dry overnight.
[0456] [Calculation of cleaning rate]
[0457] For the washed mud-contaminated cloth and standard white cloth, measurements were taken using the DigiEye system with a D65 light source. , , The value of is calculated from the above formula (II) to obtain the cleaning rate SRI.
[0458] [Calculation of Re-contamination Prevention Capability]
[0459] For the uncontaminated white portion of the washed mud-contaminated cloth and the standard white cloth, a spectrophotometer (manufactured by Nippon Denshoku Kogyo Co., Ltd., product name: SE6000) was used with a D65 light source and a viewing angle of 2° to measure the difference. , , The value of . The white portion of the soiled cloth after washing and the standard white cloth are calculated using equation (III) above. The recontamination of the white cloth portion was evaluated.
[0460] Cleaning power was evaluated using two different liquid detergent complexes: Complex 1 (0% nonionic surfactant) and Complex 2 (17% nonionic surfactant). The cleaning efficiency and recontamination prevention capabilities were assessed, and the results are shown in Table 12. The results indicate that a higher proportion of nonionic surfactant in the detergent complex results in both higher cleaning efficiency and recontamination prevention capabilities.
[0461] [Table 12]
Claims
1. A liquid laundry detergent composition comprising a vinyl alcohol-based polymer and a surfactant, wherein, The vinyl alcohol polymer has a structural unit (a) as shown in formula (1), and optionally has a structural unit (b) as shown in formula (2), and other structural units (c) besides structural units (a) and (b). [Chemical Formula 1] [Chemical Formula 2] Relative to the total amount of all structural units (100 mol%), the content ratio of each structural unit is structural unit (a) / structural unit (b) / other structural units (c) = 50~100 / 0~50 / 0~20 mol%, and the average degree of polymerization is 50~800. The content of this vinyl alcohol polymer is 0.3% to 10% by mass relative to 100% by mass of the liquid laundry detergent composition. The surfactant is present in a proportion of 10% to 80% by mass relative to 100% by mass of the liquid laundry detergent composition, and the proportion of cationic surfactant is less than 20% by mass relative to 100% by mass of the surfactant. The proportion of inorganic detergent builders is less than 50% by mass relative to 100% by mass of the liquid laundry detergent composition.
2. The liquid laundry detergent composition according to claim 1, wherein, The probability of compatibility 1 / (1+Exp(-y)) represented by y as specified in the following formula (I) is 0.5 or higher. y=73.7-0.418×α-0.725×β-0.00332×γ (I) In the formula, α represents the proportion (mass%) of surfactant in the evaluation solution when evaluating compatibility of liquid laundry detergent compositions; β represents the degree of saponification of the vinyl alcohol polymer (mol%); and γ represents the average degree of polymerization of the vinyl alcohol polymer.
3. The liquid laundry detergent composition according to claim 1 or 2, wherein, The surfactant includes anionic surfactants.
4. The liquid laundry detergent composition according to any one of claims 1 to 3, wherein, The surfactants include anionic surfactants and nonionic surfactants.
5. The liquid laundry detergent composition according to any one of claims 1 to 4, wherein, The surfactant comprises anionic surfactants and nonionic surfactants, wherein the proportion of anionic surfactants is 30% or more by mass relative to 100% of the total mass of anionic surfactants and nonionic surfactants.
6. The liquid laundry detergent composition according to claim 4 or 5, wherein, The nonionic surfactant is present in a proportion of 5% to 70% by mass relative to 100% of the total surfactant content.
7. The liquid laundry detergent composition according to any one of claims 1 to 6, wherein, The liquid laundry detergent composition contains a polyalkylene glycol compound.
8. The liquid laundry detergent composition according to claim 7, wherein, The polyalkylene glycol compound is present in a proportion of 100% to 1000% by mass relative to 100% by mass of the vinyl alcohol polymer.
9. The liquid laundry detergent composition according to any one of claims 1 to 8, wherein, The liquid laundry detergent composition contains enzymes.
10. A composite composition comprising a liquid laundry detergent composition encapsulated in a film for detergent packaging, wherein, The liquid laundry detergent composition comprises a vinyl alcohol polymer and a surfactant, the vinyl alcohol polymer having a structural unit (a) as shown in formula (1) below, and optionally having a structural unit (b) as shown in formula (2) below, and other structural units (c) besides the structural units (a) and (b). [Chemical Formula 3] [Chemical Formula 4] Relative to the total amount of all structural units (100 mol%), the content ratio of each structural unit is structural unit (a) / structural unit (b) / other structural units (c) = 50~100 / 0~50 / 0~20 mol%, and the average degree of polymerization is 50~800.
11. The composite composition according to claim 10, wherein, The surfactant is present in a proportion of 50% to 80% by mass relative to 100% by mass of the liquid laundry detergent composition.
Citation Information
Patent Citations
Additive for granular detergent
JP1984006299A
Enzyme-containing detergent composition
JP1988305198A
Bleaching agent composition and bleaching detergent composition
JP1994316700A
Finishing agent for washing
JP1999005992A
Easy washability-imparting agent for textile product
JP2022080076A